Prunin attenuates aflatoxin B1-induced testicular toxicity by alleviating oxidative stress and modulating TLR4/MyD88/NF-κB and Bax/Bcl-2/Caspase-3 signaling pathways - Muhammad Umar Ijaz; Ghulam Mustafa; Muhammad Zaid Salar; Amjad Islam Aqib; Ghulam Hussain; Aisha Khatoon; Hamida Hamdi (Tissue and Cell, 2027)

Identification of plastome-derived mini barcodes by DNA metabarcoding and comparative effectiveness to decipher their strength and resolving power for taxonomic topology-based phylogenetic determination of Chenopodium quinoa - Zakia Habib; Siddra Ijaz; Imran Ul Haq; Irfan Afzal; Ghulam Muhammad Ali (Molecular Biology Reports, 2026)

Immunoinformatics-guided design of a multi-epitope vaccine targeting the envelopment polyprotein of oropouche virus - Muhammad Naveed; Aroosa Athar; Afifa Tariq; Muhammad Asim; Muhammad Nouman Majeed; Rania Ali El Hadi Mohamed; Manal F. Elkhadragy; Maher S. Alwethaynani; Mai M. Almsaud; Ghulam Nabi (Molecular Genetics and Genomics, 2026)

Molecular networks and signaling pathways governing abiotic stress tolerance in cotton: advances and perspectives - Imran Ullah; Muhammad Nadeem; Hafiz Ghulam Nabi; Nida Shahzad; Zohair Abbas; Isha Shakoor; Diba Kiran; Mehdi Rahimi; Rukhsana Gulab; Rida Batool (Functional & Integrative Genomics, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

A hybrid approach for COVID-19 detection: Combining Wasserstein GAN with transfer learning - Sumera Rounaq; Shahid Munir Shah; Mahmoud Aljawarneh; Ghulam Muhammad (Next Research, 2026)

Interpretable machine learning biodegradation of Direct Black 22 by Lysinibacillus sphaericus: Kinetics, mechanism, and wastewater application - Ihtisham Jamil; Ghulam Mustafa; Muhammad Tariq Zahid; Aliya Alvi; Deok-Won Kim; Tehreem Batool; Ramesh Kumar; Farah Rauf Shakoori; Ju-Hyeok Kwon; Hyun-Jo Ahn; Byong-Hun Jeon (Journal of Environmental Chemical Engineering, 2026)

Microbial diversity enhancement in a bio-electro-fenton system driven by sediment microbial fuel cells for photocatalytic PAHs degradation in antibiotics applicate soil-water systems - Muhammad Usman; Zenhua Zhao; Muhammad Adnan; Muhammad Ibrahim; Olive Mekontchou Yemele; Ghulam Abbas Ashraf; Mukhtorjon Karimov; Alisher Abduvokhidov; Naoufel Ben Hamadi (Journal of Environmental Chemical Engineering, 2026)

Divergent nitrogen allocation–photosynthesis relationships in light-demanding and shade-tolerant species across succession in subtropical broad-leaved evergreen forest - Muhammad Abdullah; Samreen Ghulam Rasool; Qianqian Ji; Dezhi Li (Forest Ecology and Management, 2026)

Enhanced biomethane production associated with olivine-stimulated CO2 reduction in petroleum reservoir production water - Muhammad Javed; Muhammad Irfan; Le-Gang Chen; Bo Fang; Bo-Wen Wang; Ghulam Dastgir; Muhammad Kashif Javed; Lei Zhou; Yi-Fan Liu; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (Bioresource Technology, 2026)

Performance analysis of a helium-nitrogen binary gas mixture centrifugal compressor for terrestrial gas-cooled reactor power plants of closed Brayton cycles - Arif Aziz; Qun Zheng; Adil Malik; Muhammad Haris; Ghulam Ishaque; Shadman Ahmad Khattak (Annals of Nuclear Energy, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

Retraction notice to ‘Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment’ [Environ. Pollut. 362, (2024) 125000] - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2026)

Influence of Temperature and Hydrogen Peroxide Treatment on the Physiochemical and Adsorptive Characteristics of Rice Stalk Biochar for Cadmium Remediation: A Sustainable Solution - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Awais Ahmad; Waed Alahmad; Mohammed S. Alotaibi; Saqer S. Alotaibi; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Synergistic role of biochar, AMF, and PGPR in enhancing drought tolerance and productivity of wheat (Triticum aestivum L.) - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Islem Abid; Awais Ahmad; Vusala Ismayilova; Manal Abdulaziz Binobead; Rashid Iqbal (Cereal Research Communications, 2026)

An efficient peroxymonosulfate activation by Nb2CTx-MXene mediated with CQDs composite catalyst for carbamazepine degradation: Kinetics and mechanistic insights - Muhammad Adnan; Zhenhua Zhao; Liling Xia; Ghulam Abbas Ashraf; Arslan Tauqeer; Muhammad Usman; Saqib Bashir; Thamer Alomayri; Akmal Abilkasimov (Journal of Environmental Sciences, 2026)

Nanoparticles of thiolated gum ghatti for the controlled ocular delivery of Ciprofloxacin - Muhammad Abu Sufian; Shahid Shah; Akhtar Rasul; Nabeel Ahmad; Ghulam Abbas; Muhammad Hanif; Saleha Babar; Azka Fatima; Omeira Iqbal; Maira Tahir; Nader I. Namazi (DARU Journal of Pharmaceutical Sciences, 2026)

Hybrid multilayer radiation shielding for lunar habitats: material integration, encapsulation strategy, and optimization against GCR and SPE - Ghulam Muhammad Owaisi; Qiang Yang; Alessandro Bartoloni; Shuai Yuan (Advances in Space Research, 2026)

Seasonal fluctuations in the hypothalamic irisin and its correlation with the hypothalamic-pituitary-gonadal -axis activity in male rhesus monkeys (Macaca mulatta) - Muhammad Saqib; Amel Aftab; Ghulam Nabi; Muhammad Noman Khan; Hira Zubair; Fazal Wahab; Maha Abdullah Alwaili; Nawal Al-Hoshani; Muhammad Shahab (Journal of Comparative Physiology B, 2026)

Immunopharmacological and structural design of a polyprotein based multi epitope vaccine against Powassan virus - Aasia Kalsoom; Syed Hussain Abidi; Sohail Ameer Marwat; Ghulam Shabbir; Muhammad Naveed; Aiman Muhammad Ashraf Mughal; Muhammad Nouman Majeed; Shereen Magdy Korany; Basma Magdy Korany; Khaled Alzhrani; Tariq Aziz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Genotypic Characterization of Genetic Diversity for the Development of Leaf Rust Resistance in Bread Wheat using SSR Markers - Mueen Alam Khan; Muhammad Farooq Naseer; Jafarov Valeh; Hafiz Ghulam Muhu Din Ahmed; Beena Alam; Adel A. Rezk; Nora M. Al Aboud (Plant Molecular Biology Reporter, 2026)

Arbuscular Mycorrhizal Fungi and Leonardite alter fatty acid and amino acid biosynthesis in sunflower grains - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Sajad Ali; Zeeshan Ahmed; Khairiah Mubarak Alwutayd; Rashid Iqbal (Plant Molecular Biology, 2026)

Effects of strigolactone-modified biochars on wheat (Triticum aestivum L.) germination and soil nutrient dynamics in alkaline soil - Ghulam Murtaza; Muhammad Usman; Wael Elmenofy; Hanan M. Alharbi; Khairiah Mubarak Alwutayd; Mohammad K. Alharbi; Rashid Iqbal (Cereal Research Communications, 2026)

Enhancement of maize drought resilience using nano-buckminsterfullerenes and plant growth-promoting rhizobacteria: insights into pigment stability, oxidative stress reduction, and yield - Ghulam Murtaza; Muhammad Usman; Najmaldin Ezaldin Hassan; Zeeshan Ahmed; Awais Ahmad; Khairiah Mubarak Alwutayd; Wael Elmenofy; Hassan Mehmood; Rashid Iqbal (Cereal Research Communications, 2026)

Adaptive role of silicon in enhancing crop resilience and yield under stressful environments: A new window for stress management - Ghulam Murtaza; Muhammad Rizwan; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Rashid Iqbal; Akash Tariq; Gang Deng (Plant Biosystems, 2026)

Comparative evaluation of carbon sequestration and climate change mitigation in commercially planted eucalyptus-based agroforestry systems in a semi-arid region - Ghulam Yasin; Muhammad Azeem Akhter; Muhammad Zubair; Muhammad Talha Imtiaz; Matoor Mohsin Gilani; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Dilnoza Sotiboldiyeva; Shafeeq Ur Rahman (Journal of Environmental Studies and Sciences, 2026)

Synergistic application of biochar and mercury-resistant Bacillus cereus enhances phytoremediation efficiency and stress tolerance in sorghum (Sorghum bicolor L.) grown in mercury-contaminated soil - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal (Biodegradation, 2026)

Role of rituximab in treatment of patients with primary central nervous system lymphoma: An updated systematic review and meta-analysis - Kumail Mustafa Ali; Muhammad Farhan Ashraf; Zain Ul Abideen; Armish Rehman; Rumman Javed; Ayena Ghulam Mujtaba; Touba Diwan; Ukasha Khalid; Laiba Ikram (Acta Neurologica Belgica, 2026)

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Assessment of temporal and spatial shifts in climatic parameters and their impact on crop water requirement in the Lower Chenab Canal Command Area, Pakistan - Ahtisham Mehmood; Muhammad Masood; Ahmad Mujtaba; Ghulam Nabi; Abu Bakar Arshed (Theoretical and Applied Climatology, 2026)

Rock–water interactions in the coal mining area of Dukki, Balochistan, determine the drinking and irrigation suitability of groundwater: an in-depth risk assessment - Ghazala Mohammad Ali; Muhammad Akhtar; Muhammad Faraz Bhatti; Fazal Adnan; Malik Badshah; Ghayas Haider Sajid; Ghulam Haider (Environmental Geochemistry and Health, 2026)

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Role of Nano-Silicon, Nano-Biochar, and Irrigation Strategies in Managing Tellurium Toxicity: Implications for Soil Microbiota, Wheat Yield, and Food Safety - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Zeeshan Ahmed; Rehman Habib; Javed Iqbal; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Retraction Note: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Synergistic effects of foliar selenium nanoparticles and aged cellulose-derived biochar on PAH immobilization and spinach health in contaminated soils - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Zeeshan Ahmed; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Environmental Geochemistry and Health, 2026)

Efficient cadmium sequestration from water using cotton husk biochar and copper oxide nanocomposite: adsorption performance, kinetics, and isotherm modeling - Atika Waqar; Muhammad Farhan; Faiza Sharif; Muhammad Imran; Ghulam Mustafa Shah (Environmental Geochemistry and Health, 2026)

Myoinositol-mediated regulation of leaf physiology, biochemistry, and water relations confers heat stress tolerance in Quinoa - Rashid Iqbal; Muhammad Sarwar; Basharat Ali; Muhammad Farrukh Saleem; Hassaan Ahmad; Muhammad Shahid; Javed Iqbal; Khairiah Mubarak Alwutayd; Dilfuza Jabborova; Sajad Ali; Ghulam Murtaza (Plant Biosystems, 2026)

Role of Acacia bark biochar in the growth of Ocimum basilicum L. under cadmium stress - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal; Hossam S. El-Beltagi; Mashael Daghash Alqahtani; Usman Zulfiqar (Biodegradation, 2026)

Combined application of 5-ALA and nitric oxide improves lead detoxification and antioxidant defense in barley - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Wael Elmenofy; Muhammad Aamir Manzoor; Rashid Iqbal (Biodegradation, 2026)

Artemisia absinthium attenuates hepatic fibrosis in mice by suppressing hepatic stellate cells activation and modulating inflammatory chemokine signaling - Rabbia Manzoor; Iram Gull; Abrar Ahmed; Tuba Ghulam Hussain; Ubaida Hussain; Muhammad Shahbaz Aslam (Cell Biochemistry and Biophysics, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Arbuscular mycorrhizal symbiosis Drives rhizosphere-regulated drought tolerance in maize - Ghulam Murtaza; Muhammad Usman; Khairiah Mubarak Alwutayd; Rashid Iqbal (Rhizosphere, 2026)

Transient mixed convection in coaxial pipes with temperature-dependent variable density - Bakhtawar Bibi; Ali B.M. Ali; Muhammad Ashraf; Ghulam Rasool; Muhammad Usman Rashid; Abduvali Sottarov (Dynamics of Atmospheres and Oceans, 2026)

Integrative analysis of rhizosphere metabolomics and root anatomical adaptations in wheat under drought stress: comparative insights from DH-11 and PK-13 - Sohail Ahmed; Muhammad Kaleem Samma; Faisal Mehdi; Kamran Yaqoub; Manzer H. Siddiqui; Amna Jabbar Siddiqui; Syed Ghulam Musharraf; Saddia Galani; Zubia Rashid; Hania Ahmed (Physiology and Molecular Biology of Plants, 2026)

Co-application Impacts of Silicon and Potassium Fertilizers on Wheat (Triticum Aestivum L.) Growth and Nutritional Attributes in Cadmium-contaminated Soil Under Two Irrigation Regimes - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Rizwan; Qamar uz Zaman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Shabir Ahmad; Lala Gurbanova; Rashid Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Coated Urea Improves Productivity and Nitrogen Use Efficiency in Wheat - Muhammad Talha Aslam; Imran Khan; Muhammad Umer Chattha; Ghulam Murtaza (Journal of Soil Science and Plant Nutrition, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Improving growth and physicobiochemical attributes of rice via PGR-based seed priming: a comparative study of establishment methods - Yousaf Saeed; Muhammad Aurangzaib; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Ghulam Murtaza; Lala Gurbanova; Rashid Iqbal (Cereal Research Communications, 2026)

Influence of functional diversity on aboveground biomass accumulation in subtropical sub montane forests - Muhammad Majeed; Akash Jamil; Yongheng Gao; Ghulam Yasin; Umair Younas; Elena Pismennaya; Ksenia Myachina; Nasir Qadir (Journal of Mountain Science, 2026)

Fruit yield estimation of kinnow mandarin (Citrus reticulata) orchards – integrating canopy physiology with remote sensing - Ansar Ali; Muhammad Imran; Touqeer Ahmad; Ghulam Abbas (Arabian Journal of Geosciences, 2026)

Correction: Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Hormetic Priming of Sorghum Water Extract Imparts Drought Tolerance and Mediated Antioxidative Defense in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Basmah M. Alharbi; Shehnaz kousar; Hayam A. Alwabsi; A. Altalhi; Abdulrahman Saad Aldawood; Khawaja Ghulam Rasool (Agricultural Research, 2026)

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to ‘Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads’ [International Journal of Refrigeration 181 (2026) 111–125] - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Remediation of Water Contaminated by Toxic Metals with Multi-metal/Co-doped Modified Biochars - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Muhammad Qasim; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Lala Gurbanova; Mehdi Rahimi (Water, Air, & Soil Pollution, 2026)

Impact of Egyptian grass (Dactyloctenium aegyptium) competition on performance of fine and coarse rice under dry direct-seeded aerobic systems - Muhammad Nawaz; Abdul Khaliq; Saddam Hussain; Ghulam Murtaza; Hafiz Muhammad Akram (Phytoparasitica, 2026)

Synergistic effect of prednisolone and omega-3 fatty acids revealed through in silico, in vitro, and in vivo approaches against APAP-induced mouse model of acute liver injury - Zainab Rehman; Muhammad Ali; Arifa Mehreen; Ghulam Mustafa; Bushra Akhtar; Ali Sharif; Sehrish Murtaza; Muhammd Haroon Hamed; Amina Sagheer; Mahnoor Yamin (Toxicology and Applied Pharmacology, 2026)

Carbon-based materials for photocatalytic degradation of pharmaceuticals and drugs - Shan Arif; Sufian Rasheed; Naseer Ahmad; Muhammad Ikram Nabeel; Waqas Ahmad; Thamer Alomayri; Dilshad Hussain; Syed Ghulam Musharraf (Journal of Water Process Engineering, 2026)

Analysis of building-integrated solar desiccant air cooling systems considering the dynamic sensible and latent cooling loads - Ghulam Qadir Chaudhary; Zhongtao Hu; Suoying He; Muzaffar Ali; Sibghat Ullah; Muhammad Waheed Azam; Muhammad Usman; Ning Qin; Ming Gao (International Journal of Refrigeration, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

The criticality of public concern to corporate sustainability: Unleashing the dual internal and external environmental management pathways influencing corporate green behavior and performance - Wu Yaoguo; Yang Qiang; Imran Ur Rahman; Ghulam Muhammad Qamri (Journal of Environmental Management, 2025)

The potential influence of food additives and contaminants on the gut microbiota: A comprehensive review - Sana Ullah; Sher Ali; Muhammad Atif; Muhib Ullah; Ghulam Nabi; Lucas Gabriel Dionisio Freire; Eliana Setsuko Kamimura; Amir Sasan Mozaffari Nejad; Carlos Augusto Fernandes de Oliveira (Food and Chemical Toxicology, 2025)

Synergistic Arsenic Adsorption by Nano Zero-Valent Iron and Biochar: Batch and Column Scale Performance - Muhammad Asif Naeem; Muhammad Imran; Muhammad Amjad; Ghulam Mustafa Shah; Ghulam Abbas; Behzad Murtaza; Muhammad Shafique Khalid; Hafiz Faiq Bakhat; Samina Khalid; Muhammad Imtiaz Rashid (Water, Air, & Soil Pollution, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Assessing hazardous flash flood susceptibility using multivariate zonation mapping techniques in Pishin District, Balochistan province of Pakistan - Muhammad Ashraf; Qahir Shah; Adnan Arshad; Ghulam Murtaza (Natural Hazards, 2025)

Beta-Glucan in barley as a natural immunomodulator: mechanisms and therapeutic potential - Hafiz Ghulam Muhu Din Ahmed; Li’E Yang; Xiaomeng Yang; Jiazhen Yang; Sajid Hussain; Muhammad Danial Shafiq; Muhammad Irfan Akram; Muhammad Sajad; Yawen Zeng (Molecular Biology Reports, 2025)

FABP3 deficiency exacerbates renal Randall plaque formation: insights from single-cell RNA transcriptomic analysis - Muhammad Sarfaraz Iqbal; Xiaolu Duan; Kotb A. Attia; Ghulam Nabi; Kaoqing Peng; Nimra Sardar; Di Gu; Guohua Zeng; Nada S. Al-Theyab (Molecular and Cellular Biochemistry, 2025)

Utilizing Biochar to Enhance Morphophysiology and Antioxidative Defense Mechanisms in Lactuca sativa(lettuce) Exposed to Industrial Wastewater and Canal Water - Hafiza Iqra Almas; Fahd Rasul; Muhammad Shahbaz; Ghulam Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Evaluating Soil Reclamation and Growth Enhancing Potential of Various Types of Biochar with Respect To Rice Crop Cultivated in Saline Sodic Soil - Imran Shehzad; Ghulam Sarwar; Abid Mahmood; Kashf Mehmood; Zuhair Hasnain; Muhammad Zeeshan Manzoor; Danish Ibrar; Saqib Bashir; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Fagonia Indica and Garlic Extract On Alternaria Alternata and Post-harvest Quality of Tomato Fruit During Storage - Sameer Lal; Ghulam Khaliq; Abdul Hafeez Mastoi; Asif Irshad; Muhammad Abuzar Jaffar; Lawang Khan; Noor Muhammad (Journal of Crop Health, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Exploring the Synergistic Benefits of Sugarcane Intercropping with Legumes and Nitrogen Reduction on System Productivity - Abdul Khaliq; Muhammad Zia Ul Haq; Abdul Khaliq; Ghulam Murtaza (International Journal of Plant Production, 2025)

Improving Soil Fertility, Seed Yield, and Oil Quality of Sunflower Through Application of Processed Animal Manure Under Rainfed Conditions - Ghulam Abbas Shah; Mughees Mustafa; Zheli Ding; Zahid Mahmood; Faheem Khan; Shujaat Hussain Khan; Safdar Ali; Ghulam Mustafa Shah; Imran Mahmood; Muhammad Bilawal Junaid; Munirah Abdullah Al-Dosary; Muhammad Habib Ur Rehman; et al. (International Journal of Plant Production, 2025)

Physio-biochemical alterations and phytoremediation potential of hemp cultivated in ciprofloxacin (CIP)-contaminated soil: groundbreaking and enduring solution - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Javed Iqbal; Hassan Mehmood; Hossam S. El-Beltagi; Khairiah Mubarak Alwutayd; Gamal Awad El-Shaboury; Rashid Iqbal (Biodegradation, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Mitigating Fruit Drop Challenges: Unraveling the Role of Plant Growth Regulators and Micronutrients in Jujube (Ziziphus mauritiana L.) cvs. in the Cholistan Desert, Pakistan - Abdul Haseeb Ahmed; Rashad Qadri; Khalid Hussain; Muhammad Tahir Akram; Muhammad Azam; Muhammad Awais Ghani; Muhammad Mumtaz Khan; Muhammad Asif Rai; Basharat Ali; Abd El-Zaher M. A. Mustafa; Mohamed S Elshikh; Ghulam Murtaza; et al. (Applied Fruit Science, 2025)

Synergistic PMS activation by SnBi@ZrC under visible light for enhanced organic pollutant removal - Rana Mohsin Ali; Jie Wang; Tianhong Zhou; Yue Tian; Muhammad Usman; Hamza Khaliq; Muhammad Adnan; Zunaira Nasir; Ghulam Abbas Ashraf; Yusuke Yamauchi (Journal of Water Process Engineering, 2025)

From roots to resilience: Strigolactones for boosting crop resilience and productivity under stressful environments - Zeeshan Ahmed; Dongwei Gui; Ghulam Murtaza; Muhammad Shareef; Akash Tariq (Journal of Environmental Management, 2025)

Decarbonizing global value chains: The mediating role of economic upgrading in renewable energy transitions - Ghulam Muhammad Qamri; Li Sanchuan; Muhammad Saeed; Samariddin Makhmudov (Journal of Environmental Management, 2025)

Surface engineering of single-crystal NCM811 with graphene for enhanced mechanical integrity - Muhammad Fasehullah; Sidra Jamil; Ghulam Ali; Keun Hwa Chae; Bushra Jabar; Adil Mansoor; Chao Tang (Chemical Engineering Journal, 2025)

Modeling the impact of climate warming on tomato phenology - Shakeel Ahmad; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Muhammad Ali Khan; Mukhtar Ahmed; Carol Jo Wilkerson; Gerrit Hoogenboom (Agricultural and Forest Meteorology, 2025)

Ultrahigh-porosity peony-like magnesium oxide for the superior adsorption of arsenic (III) and arsenic (V) from aqueous solutions - Ghulam Asghar; Duc Anh Nguyen; Thi Hai Chau Dong; Sumaira Manzoor; Shahid Ali; Muhammad Mansha; Shehzada Muhammad Sajid Jillani; Safyan Akram Khan (Journal of Hazardous Materials, 2025)

Designing MgAlCe-Adenine LDH@g-C3N4 nanohybrid integrated polypropylene for bi-functional flame retardancy and corrosion protection - Salman Khalid; Jun Sun; Xinyu Chen; Mohammad Tabish; Mubashar Mahmood; Muhammad Mubeen; Yangming Zou; Zhenhua Wang; Xiaoyu Gu; Jingmao Zhao; Ghulam Yasin; Sheng Zhang (Chemical Engineering Journal, 2025)

Electro-microbial destruction of ‘forever chemicals’: Recent advances and imminent challenges - Muhammad Hassan; Miao Lv; Jedsada Chuiprasert; Zhiqi Zou; Ibrahim Abusallout; Sikai Chen; Hugo Olvera-Vargas; Ghulam Abbas Ashraf; Hisham S.M. Abd-Rabboh; Suwanna Kitpati Boontanon (Chemical Engineering Journal, 2025)

Impacting Value of Different Oxidation States of Copper and Jamun Leaves Extract During the Green Synthesis of CuO Nanostructures for Efficient Photocatalytic Degradation of Methylene Blue in Aqueous Solutions - Saira Bughio; Muhammad Ali Bhatti; Sajida Bughio; Aneela Tahira; Tayyaba Khalid; Ghulam Zuhra Memon; Muhktiar Hussain Bozdar; Elmuez Dawi; Ayman Nafady; Matteo Tonezzer; Zafar Hussain Ibupoto (Water, Air, & Soil Pollution, 2025)

Ring opening of epoxides: a facile approach towards the synthesis of polyketides and related stereoenriched natural products: a review - Madiha Hanif; Asim Mansha; Kulsoom Ghulam Ali; Muhammad Athar Saeed; Shahid Mahmood; Aijaz Rasool Chaudhry; Ahmad Irfan; Aqsa Mushtaq; Ameer Fawad Zahoor (Molecular Diversity, 2025)

Analytical solutions of the eighth-order (3+1)-dimensional Kac–Wakimoto equation modeling waves in ocean engineering - Jan Muhammad; Ghulam Hussain Tipu; Usman Younas (Modeling Earth Systems and Environment, 2025)

Effect of pollen sources on biochemical indices and hybrid authentication in date palm (Phoenix dactylifera L.) cv. Khadrawy - Maryam; Ishtiaq Ahmad; Muhammad Nafees; Muhammad Saqib; Mona S. Alwhibi; Mohamed S. Elshikh; Mehmet Ramazan Bozhuyuk; Javed Iqbal; Shabir Ahmad; Trobjon Makhkamov; Ghulam Murtaza; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Production Technologies for Recombinant Antibodies: Insights into Eukaryotic, Prokaryotic, and Transgenic Expression Systems - Muhammad Zafar Saleem; Ghulam Zahra Jahangir; Ammara Saleem; Asma Zulfiqar; Khalid Ali Khan; Sezai Ercisli; Baber Ali; Muhammad Hamzah Saleem; Aroona Saleem (Biochemical Genetics, 2025)

Bay leaves: the neuroprotective dietary spice via inhibition of amyloid-like aggregation - Nazish Mustafa; Sana Khan; Laila Anwar; Mir Muhammad Uzairullah; Huma Aslam Bhatti; Syed Abid Ali; Ghulam Abbas (Metabolic Brain Disease, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Evaluation of altered biochemical and physiological responses and expression of defense-related genes in wheat following the application of plant growth regulators under drought stress - Husnain Jawad; Muhammad Bilawal Junaid; Habib Ali; Saba Saba; Shehnaz Kousar; Muhammad Saqib; Aniqa Mubeen; Ghulam Abbas; Rafique Ahmed; Amal Mohamed AlGarawi; Ashraf Atef Hatamleh; Sadam Hussain (South African Journal of Botany, 2025)

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Unleashing the critical role of renewable energy through global value chains and digitalization: A path towards environmental sustainability - Long Zhang; Zuoxiang Zhao; Ghulam Muhammad Qamri; Samariddin Makhmudov (Journal of Environmental Management, 2025)

Polymeric carbon nitride-based semiconductors as a beneficial candidate in photocatalysis diversity: A comprehensive review - Sidra Tul Muntaha; Jawad Ali Shah Syed; Muhammad Mateen; Muhammad Ali Shahzad; Anand Parkash; Aqsa Asrar; Adil Emin; Ghulam Abbas Ashraf; Inaam Ullah; Muhammad Ahsan Farooq Qaisar; Salamat Ali; Ahmed Mahmoud Idris (Chemical Engineering Journal, 2025)

Comparative assessment of biochar and vermicompost on chromium bioavailability and stress alleviation in tomato (Solanum lycopersicum) - Jamaluddin Kabir; Muhammad Ansar Farooq; Shumaila Parvez; Aamir Alaud Din; Ghulam Abbas; Minggang Xu; Muhammad Mohsin Abrar (Journal of Soils and Sediments, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Foliar Application of Silicon Alleviates Drought Stress in Chickpea (Cicer arietinum L.) by Improving Growth, Photosynthetic and Antioxidant Metabolism - Muhammad Faizan Ali; Mukhtar Ahmed; Laiba Mukhtar; Nadir Ali; Ghulam Qadir; Rifat Hayat; Shakeel Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Fertilizing Effects of Ulva intestinalis Derived Bio-Stimulant Enhance Spinacea oleracea L. Production, Nutrient Fluxes and Secondary Metabolism Under NaCl Stress - Sadaf Gul; Hamad Aslam; Muhammad Farrakh Nawaz; Ghulam Yasin; Sana Riaz; Maria Hasnain; Mohamed A. El-Sheikh; Emanuele Radicetti; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2025)

Phosphorus Modified Biochar and Vermicompost Integration Alleviated Cd Phytotoxicity in Wheat (Triticum aestivum L.) by Improving Growth, Antioxidant Activities and Reducing Cd Uptake in Plants - Ahmad Ali; Zaffar Malik; Ghulam Hassan Abbasi; Muhammad Waseem; Muhammad Rizwan; Muhammad Ali; Sobia Afzal; Syed Farhan Haider Bukhari; Usama Ali Tahir (Journal of Soil Science and Plant Nutrition, 2025)

Rhizobacterial diversity exhibiting biotic stress tolerance in association with wheat-cotton crop rotation: Implications for plant–microbe interactions and agroecosystem resilience - Seema Aslam; Muhammad Babar; Ghulam Shabir; Tahir Naqqash; Florian M. W. Grundler (Biologia Futura, 2025)

Novel MAX-phase Nb2AlC@Biochar: A dual-functional peroxymonosulfates activator for antibiotics and dyes degradation via Nb4+/Nb5+ redox switches; DFT insight and mechanistic elicitation - Muhammad Adnan; Zhenhua Zhao; Ghulam Abbas Ashraf; Saqib Bashir; Binglu Teng; Jureeporn Yuennan; Saqer S. Alotaibi; Muhammad Mushtaq (Journal of Water Process Engineering, 2025)

Effect of MXenes, nZVI and Acacia-wood Biochar Treatments on Bioavailability Pb and Fractions in Calcareous-polluted Soils - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Usman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal (Water, Air, & Soil Pollution, 2025)

Impact Assessment of Optimal Water Allocation Using a Linear Model in Lower Bari Doab Canal Command Area - Atiqa Yasin; Muhammad Awais Zafar; Muhammad Masood; Ghulam Nabi; Mudassar Iqbal (Water Conservation Science and Engineering, 2025)

Spatial distribution of potentially toxic elements and ecological-health risks in a wastewater-irrigated peri-urban agroecosystem: a multi-matrix assessment from Muzaffargarh, Pakistan - Muhammad Tansar Abbas; Jalal Uddin; Irshad Ullah; Abd Ullah; Hidayat Ullah; Abdullatif Bin Muhsinah; Syed Ghulam Musharraf; Pankaj Kumar (Environmental Geochemistry and Health, 2025)

Finding the Best Growth Media for Kiwifruit Cv. ‘Hayward’ Seedling Rootstocks in Mansehra District, Pakistan - Sadaf Bibi; Aftab Afzal; Ghulam Mujtaba Shah; Abdul Waheed; Muhammad Anas; Waseem Ahmed Khattak; Shah Fahad (Applied Fruit Science, 2025)

Long-term PM2.5 exposure in Bangladesh: identification of pollution hotspots, trends, sources and health risk assessment - Md. Arfan Ali; Mazen E. Assiri; Muhammad Bilal; Salman Tariq; Gerrit de Leeuw; M. Nazrul Islam; Yu Wang; Lama Alamri; Ayman S. Ghulam; Shamsuddin Shahid (Air Quality, Atmosphere & Health, 2025)

Adaptive responses of trees to industrial pollution: modulation of leaf anatomical, physio-biochemical, and heavy metal accumulation traits in urban biotopes - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Mansoor Javaid; Usman Zulfiqar; Nafosat Djonibekova; Anarjan Matkarimova; Hesham S. Almoallim; Mohammad Javed; Shafeeq Ur Rahman (Environmental Monitoring and Assessment, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Assessment of tomato germplasms for Mi-1.2-mediated resistance to Meloidogyne incognita: Integrating in-silico dynamics and bioinformatic approaches - Adil Zahoor; Zeenat Niaz; Muhammad Jabran; Hira Anwar; Amjad Abbas; Abdul Haseeb; Ghulam Mustafa; Sungmi Sun; Seung Hwan Yang; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

When low-dimensional nanomaterials meet polymers: A promising configuration for flame retardancy and corrosion protection - Salman Khalid; Muhammad Mubeen; Mohammad Tabish; Muhammad Jawad; Muhammad Uzair Malik; H.M. Ahsen Ilyas; Mubashar Mahmood; Mohammed Mujahid Alam; Jun Sun; Ghulam Yasin (Chemical Engineering Journal, 2025)

Synergistic Effects of 5-Ureidohydantoin, Rhizobacteria and Non-wood-Based Biochar on Barley Productivity Under Drought and Multiple Toxic Metals Stress - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Abdul Razzaq; Iram Saba; Gang Deng; Zeeshan Ahmed; Abdel-Rhman Z. Gaafar; Trobjon Makhkamov; Lala Gurbanova; Rashid Iqbal (Current Microbiology, 2025)

Carbapenem Resistant Serratia marcescens Harboring blaOXA-48, armA and aac(6′)-Ib-cr Genes: The First Baseline Study from Pakistan - Amna Kausar; Muhammad Sohail; Mohsin Khurshid; Hafiz Ghulam Murtaza Saleem (Current Microbiology, 2025)

Synthesis and effects of zinc-chitosan complex on morpho-growth and biochemical responses in Alternaria alternata, a cause of leaf blights and spots on plants - Ghulam Roquyya; Amna Shoaib; Shagufta Parveen; Muhammad Rafiq (World Journal of Microbiology and Biotechnology, 2025)

Response of Potato Yield, Soil Organic Matter, Microbial Properties, and Pesticide Residues to Different Cropping Systems and Nutrient Management in North Pakistan - Nanak khan; Zammurad Iqbal Ahmed; Mukhtar Ahmed; Muhammad Faizan Ali; Ghulam Jilani (Potato Research, 2025)

Assessment of Climate Change Impact on Potato-Potato Cropping System Under Semi-arid Environment and Designing of Adaptation Strategies - Sahrish Naz; Mukhtar Ahmed; Ghulam Abbas; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Abdul Ghani; Muhammad Ali; Tahir Hussain Awan; Noreen Samad; Muhammad Aasim; Sezai Ercisli; et al. (Potato Research, 2025)

Exploring Synergistic Effects of Pantoea agglomerans BCH-1 and Bacillus pseudomycoides BCH-3 To Enhance Maize Adaptations Under Drought Condition - Anam Tariq; Mahwish Salman; Muhammad Arslan Ashraf; Shazia Anwer Bukhari; Ghulam Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Combined Application of Compost and Biogas Residues Reduces Soil and Pore Water Metal Concentration and Their Residual Toxicity to Wheat Seedlings - Iftikhar Ahmad; Ghulam Mustafa Shah; Hafiz Muhammad Shahbaz; Aftab Jamal; Muhammad Imtiaz Rashid; Muhammad Farhan Saeed; Amjad Farooq; Qasim Ali; Domenico Ronga (Journal of Soil Science and Plant Nutrition, 2025)

Pollen patterns and morphological variability unraveling taxonomic relevance and evolutionary relationship in salt-tolerant species - Moona Nazish; Asif Kamal; Muhammad Zafar; Mushtaq Ahmad; Ghulam Mujtaba Shah; Jawaher Alkahtani; Khursheed Ur Rahman; Mohamed Soliman Elshikh; Sarah Abdul Razak; Muhammad Tahir Naseem; Wajid Zaman (Genetic Resources and Crop Evolution, 2025)

Molecular marker based analysis of allelic variation in the spring wheat genome - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Muhammad Irfan Akram; Rashid Iqbal; Abdullah Ahmed Al-Ghamdi; Dunia A. Al Farraj (Genetic Resources and Crop Evolution, 2025)

Phytomining potential, micro-morphological assessment, and air pollution tolerance index of plant species in multi-metals contaminated soapstone and crushing stone mines - Tufail Shakeel; Ghulam Mujtaba Shah; Bibi Saima Zeb; Iram Gul; Muhammad Irshad; Habiba Zafar (Science of The Total Environment, 2025)

Challenges and outlooks for the polyoxometalates, metal-organic frameworks (POMs-MOFs) hybrid materials in water treatment technologies - Ghulam Murtaza; Muhammad Ibrar Ahmed; Kewei Yu; Xingda An; Syed Shoaib Ahmad Shah; Manzar Sohail (Environmental Research, 2025)

Ecotoxicological investigation of arsenic contamination within the water-soil-fruit-human continuum - Muhammad Shafique Khalid; Nimra Farooq; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Samina Khalid; Hafiz Faiq Bakht; Ghulam Mustafa Shah; Muhammad Asif Naeem; Ghulam Abbas; Behzad Murtaza (Environmental Geochemistry and Health, 2025)

Weissella confusa MW051433 Mitigates Hypercholesterolemia by Biliary Cholesterol Excretion: The In Vivo Evidence - Saman Javed; Zakia Latif; Ghulam Ayesha Javed; Aneela Munir; Maria Mushtaq; Mamoona Hameed; Muhammad Arshad; Najma Arshad (Current Microbiology, 2025)

Spatio‐Temporal Dynamics of Vegetation and Land Surface Temperature in Saudi Arabia: Impacts of Climate Change on Agricultural Sites From 2010 to 2023 - Mazen E. Assiri; Md. Arfan Ali; Lama Alamri; Muhammad Haroon Siddiqui; Ayman S. Ghulam; Shamsuddin Shahid (International Journal of Climatology, 2025)
Saudi Arabia has one of the greatest water shortages and the least vegetation in the world, which is potentially exacerbating the issue of environmental impacts. Therefore, it is crucial to understand the interaction between climate change, vegetation dynamics and land surface temperature (LST). The present study investigates the spatio‐temporal distributions, variations, change detection and trends of vegetation dynamics and surface temperature over eight agricultural sites in Saudi Arabia using the Normalised Difference Vegetation Index (NDVI) and LST from Landsat 7 (Enhance Thematic Mapper Plus: ETM + ) and Landsat 8 (operational land imager: OLI) measurements for the period 2010–2023. The study also examined the relationship between NDVI, LST and climate variables such as air temperature, rainfall, relative humidity and soil moisture. Results showed that an NDVI > 0.20 represents vegetation in Saudi Arabia. Higher values of NDVI were found in Baysh, Jazan province, compared to other agricultural sites. Significant annual and seasonal variations in NDVI were also observed across eight major agricultural sites in Saudi Arabia, attributable to the region's varying climate conditions. Vegetation expansion in 2023 exceeded that in 2014 in Buraydah (304.34 km 2 ), Tabarjal (63.81 km 2 ), Hail (33.20 km 2 ), Al Qirw (22.53 km 2 ) and Baysh (3.07 km 2 ), while reductions were noted in Wadi Al Dawasir (274.58 km 2 ), Tabuk (88.56 km 2 ) and Al Ahsa (27.30 km 2 ). The LST over soil and vegetated surfaces showed that vegetation notably reduced LST at Hail (3.14°C), Al Ahsa and Wadi Al Dawasir (5.43°C), Buraydah (4.53°C), Baysh (2.71°C), Al Qirw (5.17°C), Tabuk (6.24°C) and Tabarjal (3.13°C). The study found that NDVI, LST and climate variables are positively and negatively correlated, which indicates a significant impact of climate change on vegetation patterns. The findings of this study are highly relevant for informing agricultural and environmental policy development in Saudi Arabia, with a focus on enhancing vegetation cover, mitigating the impacts of rising temperatures and advancing sustainable agricultural practices to address the challenges posed by climate change.

Insights into Wild Medicinal Plants: Assessing Mineral Profiles in the Ojhor Valley, Chitral, Pakistan - Muhammad Nauman Khan; Barkat Ullah; Alevcan Kaplan; Abdul Razzaq; Ghulam Jelani; Sana Wahab; Syed Nasar Shah; Nazima Wahid; Muhammad Adnan; Mohamed Farouk Elsadek; M. Ajmal Ali; Majid Iqbal (Biological Trace Element Research, 2025)

Connecting the sustainability: How renewable energy and digitalization drive green global value chains - Jun Li; Ghulam Muhammad Qamri; Mengya Tang; Yujie Cheng (Journal of Environmental Management, 2025)

Bioremediation of reactive blue 19 dye by laccase-producing Serratia marcescens AY4 strain - Ghulam Mustafa; Ammara Younas; Muhammad Tariq Zahid; Deok-Won Kim; Ihtisham Jamil; Nikita Yadav; Mayur B. Kurade; Shouvik Saha; Karishna Kumar Yadav; Byong-Hun Jeon (Journal of Environmental Chemical Engineering, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Estimation and geographical mapping of enteric methane emission from large ruminants under different production systems in Pakistan - Nasir Ali; Muhammad Qamar Shahid; Nisar Ahmad; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2025)

Exploring the anti-diabetic properties of camel milk: effects on blood glucose, antioxidant defense, and organ histo-morphological features in rabbits - Muhammad Asif Arain; Gul Bahar Khaskheli; Ghulam Shabir Barham; Qurban Ali Shah; Fazul Nabi; Mikhlid H. Almutairi; Bader O. Almutairi; Illahi Bakhash Marghazani (Journal of Molecular Histology, 2025)

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Evaluating the pest control efficiency of wheat storage bags and polypropylene liners against Trogoderma granarium and Tribolium castaneum - Somair Razaq; Mussaddiq Hussain; Muhammad Waqar Hassan; Ghulam Sarwar; Tauseef Anwar; Huma Qureshi; Muhammad Tahir Naseem; Mansour I. Almansour; Sulaiman Ali Alharbi (International Journal of Tropical Insect Science, 2025)

Manipulation of root-associated bacterial endophytes for sustainable crop production system: A review - Maqsood Ahmed Khaskheli; Mir Muhammad Nizamani; Entaj Tarafder; Diptosh Das; Ghulam Muhae-Ud-Din; Raheel Ahmed Khaskheli; Yong Wang (Rhizosphere, 2025)

Retraction notice to “Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure” [J. Environ. Manag. 356 (2024) 120673] - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Genomic selection, gene editing, and reproductive biotechnology: a triad for the improvement of native buffalo breeds in a developing country perspective like Pakistan - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ali Haider Saleem; Qudrat Ullah; Ghulam Abbas; Babar Maqbool; Masroor Ellahi Babar; Yanzhen Bi; Farhan Farooq (Tropical Animal Health and Production, 2025)

Role of Melatonin in Leaf Gas Exchange by Redox Regulation, K+ Homeostasis and Gene Expression in Canola Under Salinity Stress - Muhammad Ali; Muhammad Farooq; Adnan Noor Shah; Ghulam Hassan Abbasi; Salman Ahmad; Aasma Parveen; Birhanu Iticha; Muhammad Riaz; Muhammad Kamran; Fatima Nisar (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Unveiling the genetic diversity and host specificities of rust: morphological and molecular characterization of Berberis species - Siraj Uddin; Javed Iqbal; Banzeer Ahsan Abbasi; Shumaila Ijaz; Ghulam Murtaza; Muhammad Waseem; Umar Masood Quraishi; Atman Adiba; Reem M. Aljowaie; Saeedah Musaed Almutairi; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

The influence of renewable energy, humanistic culture, and green knowledge on corporate social responsibility and corporate environmental performance - Muhammad Farhan Basheer; Saira Ghulam Hassan; Afshan Ali; Saeed Ahmad Sabir; Waeibrorheem Waemustafa (Clean Technologies and Environmental Policy, 2025)

A review of performance, mechanism, and challenges of layered double hydroxide-based biocomposites for the adsorptive removal of dye contaminants from water and wastewater - Salman Ahmad; Ghulam Mujtaba; Mukarram Zubair; Mansoor Ul Hassan Shah; Muhammad Daud; Nuhu Dalhat Mu'azu; Mamdouh A. Al-Harthi (Journal of Water Process Engineering, 2025)

Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Muhammad Hamza Shahid; Ghulam Mustafa Sahi; Zunaira Afzal Naveed; Safdar Ali; Muhammad Wahab; Muhammad Sagheer; Azher Mustafa (Journal of Plant Diseases and Protection, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Genetic Divergence Among Sorghum (Sorghum bicolor L.) Genotypes Grown Under Rainfed Conditions - Rafiq Ahmad; Ghulam Shabbir; Syed Farman Ullah; Danish Ibrar; Muhammad Ilyas; Esam M. Al-Shaebi; Yawen Zeng; Abdul Qayyum (Journal of Crop Health, 2025)

Retraction Note: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2025)

Dust over Saudi Arabia from multisource data: case studies in winter and spring - Mazen E. Assiri; M. Nazrul Islam; Md Arfan Ali; Arjan O. Zamreeq; Ayman S. Ghulam; Muhammad Ismail (Air Quality, Atmosphere & Health, 2025)

Unveiling Sustainable Mineral Resources Extraction, foreign direct Investment, Technology Advancement nexus: Evidence from BRICS countries - Ghulam Muhammad Qamri; Sheng Bin; Li Sanchuan; Guo Hui (Resources Policy, 2025)

Management of the lignocellulosic structure of agricultural straw and improving energy productivity - Altaf Alam Noonari; Muhammad Safar Korai; Munawar Ali Pinjaro; Ghulam Shabir Solangi; Arthur J. Ragauskas (Environment, Development and Sustainability, 2024)

Advancing plant disease classification: A robust and generalized approach with transformer-fused convolution and Wasserstein domain adaptation - Muhammad Hanif Tunio; Jian ping Li; Xiaoyang Zeng; Awais Ahmed; Syed Attique Shah; Hisam-Uddin Shaikh; Ghulam Ali Mallah; Imam Abdullahi Yahya (Computers and Electronics in Agriculture, 2024)

Synergistic effect of biochar and intercropping on lead phytoavailability in the rhizosphere of a vegetable-grass system - Muhammad Rizwan; Ghulam Murtaza; Zeeshan Ahmed; Qimei Lin; Xuejiao Chen; Imran Khan; Hamada Abdelrahman; Vasileios Antoniadis; Esmat F. Ali; Sang Soo Lee; Lijian Leng; Sabry M. Shaheen; et al. (Science of The Total Environment, 2024)

RETRACTED: Hydrogeochemical properties, source provenance, distribution, and health risk of high fluoride groundwater: Geochemical control, and source apportionment - Muhammad Ayub; Hira Javed; Abdur Rashid; Wardah Hayat Khan; Asif Javed; Tariq Sardar; Ghulam Mujtaba Shah; Ajaz Ahmad; Jörg Rinklebe; Parvaiz Ahmad (Environmental Pollution, 2024)

Improving Irrigation Performance of Raised Bed Furrow Using WinSRFR Model - Muhammad Ayub Shah; Muhammad Waseem; Mudassar Iqbal; Ghulam Nabi; Muhammad Atiq Ur Rehman Tariq; Abu Bakar Arshed; Umar Sultan; Muhammad Laraib; Khawar Abbas (Water Conservation Science and Engineering, 2024)
Agricultural productivity is intricately tied to efficient water management strategies, with raised bed furrow systems being a prevalent method for irrigation. However, the optimization of these systems remains a critical area of exploration. The border irrigation method is commonly employed in developing countries for irrigation and leads to significant water loss, reduced irrigation efficiency, and increased irrigation durations. In contrast, raised bed furrow irrigation represents an improved surface irrigation technique that optimizes water usage in irrigated systems. This study seeks to assess the irrigation performance of raised bed furrows, encompassing deep percolation loss, distribution uniformity, adequacy, and application efficiency. The evaluation will be conducted for both existing conditions and an optimized scenario achieved through the application of the WinSRFR model. Field data facilitated the numerical simulation and the model was calibrated to reflect the existing irrigation system dynamics accurately. The performance of the model was assessed by utilizing the statistical indicator of root mean square error (RMSE) and revealed good agreement between advance and recession time. Results revealed that existing raised bed furrow irrigation exhibited up to 40% deep percolation loss, 80% distribution uniformity, and 60% application efficiency. Increasing furrow length had adverse effects; decreased application efficiency and distribution uniformity; and increased deep percolation losses. In contrast, reducing the furrow length and cutoff time by up to 33% and 40%, respectively, and increasing the width and inflow rate by up to 55% and 100%, respectively, enhanced the application efficiency and distribution uniformity, and minimized deep percolation loss. Overall, improved raised bed furrow irrigation provides a more efficient option and is encouraged to adopt for irrigation.

Role of exogenous silica fertilization and genotype selection in attenuating oxidative and osmotic stress in wheat (Triticum aestivum L.) under water deficit conditions - Muhammad Anwar ul Haq; Muhammad Nadeem; Munaza Naseem; Ghulam Hasan Abbasi; Muhammad Ali; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Tayyab Mehmood; Muhammad Awais; Rizwan Ullah; Tasawar Ali (Plant and Soil, 2024)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Morphometric and molecular characterization of Channa marulius from Riverine system of Punjab, Pakistan - Ghulam Rabbani; Fayyaz Rasool; Mahroze Fatima; Muhammad Bilal Bin Majeed (Molecular Biology Reports, 2024)

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

MicroRNA expression profiling of ovine epithelial cells stimulated with the Staphylococcus aureus in vitro - Ghulam Asghar Sajid; Muhammad Jasim Uddin; Saif Adil Abbood Al-Janabi; Abdiaziz Nur Ibrahim; Mehmet Ulas Cinar (Mammalian Genome, 2024)

Biochar and PGPR: A Winning Combination for Peanut Growth and Nodulation under Dry Spell - Tashfeen Alam; Fatima Bibi; Hunaiza Fatima; Faiza Munir; Alvina Gul; Ghulam Haider; Muhammad Jahanzaib; Rabia Amir (Journal of Soil Science and Plant Nutrition, 2024)

Nanobiochar-Coating Regulates N and P Release from DAP Fertilizer in Soil and Improves Maize Crop Productivity - Ghulam Abbas Shah; Mughees Mustafa; Hani Z. Asfour; Khubra Shoukat; Ahsan Yasin; Nadeem Ali; Muhammad Bilal Khan Niazi; Gabrijel Ondrasek; Muhammad Imtiaz Rashid (Journal of Soil Science and Plant Nutrition, 2024)

Performance evaluation of irrigation outlets with physical model study in Indus basin irrigation system of Pakistan - Ghulam Nabi; Fiaz Hussain; Bilal Sajjad; Muhammad Masood; Dengfeng Liu (Environmental Monitoring and Assessment, 2024)

Remote Sensing Assessment of Water Resources, Vegetation, and Land Surface Temperature in Eastern Saudi Arabia: Identification, Variability, and Trends - Mazen E. Assiri; Md Arfan Ali; Muhammad Haroon Siddiqui; Albandari AlZahrani; Lama Alamri; Abdullah Masoud Alqahtani; Ayman S. Ghulam (Remote Sensing Applications: Society and Environment, 2024)

Green innovation and natural resource efficiency: The role of environmental regulations and resource endowment in Chinese cities - Hao Li; Guangjie Du; Ghulam Muhammad Qamri; Sanchuan Li (Journal of Environmental Management, 2024)

Heterostructured melamine resin Spheres@GO reinforced epoxy composite achieving robust Corrosion-Resistance of Zn-Al-Mg coated steel for automotive applications - Muhammad Mubeen; Jingmao Zhao; Mohammad Tabish; Jingbao Wang; Mubashar Mahmood; Hassan Murtaza; Muhammad Jawad; Baomin Fan; Ghulam Yasin (Chemical Engineering Journal, 2024)

Detection of Mobile and Immobile Solute Transport and Their Residence Time in Saturated Low and High Permeability Soil Layers - Muhammad Zaheer; Ehsan Ul Haq; Ning Huang; Ahmed Amara Konaté; Ghulam Mujtaba Shah; Raja Umer Sajjad; Saad Ahmed Mashwani (Water, Air, & Soil Pollution, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Photocatalytic applications of A5-mPmH-Zr/CuTiO3 nanocomposite synthesized by simple hydrothermal method - Ghulam Murtaza; Muhammad Saud Khan; Kamran Tahir; Afaq Ullah Khan; Magdi E.A. Zaki; Zainab M. Almarhoon; Abdulaziz A. Alanazi; Hamza S. Al-Shehri; Sameerah I. Al-Saeedi; Hassan M.A. Hassan (Journal of Environmental Chemical Engineering, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Revolutionizing soybean genomics: How CRISPR and advanced sequencing are unlocking new potential - Muhammad Khuram Razzaq; Muhammad Naveed Babur; Muhammad Jawad Akbar Awan; Ghulam Raza; Mehwish Mobeen; Ali Aslam; Kadambot H. M. Siddique (Functional & Integrative Genomics, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Legume choice and planting configuration influence intercrop nutrient and yield gains through complementarity and selection effects in legume-based wheat intercropping systems - Muhammad Ali Raza; Atta Mohi Ud Din; Ghulam Abbas Shah; Wang Zhiqi; Ling Yang Feng; Hina Gul; Hassan Shehryar Yasin; Mohammad Shafiq ur Rahman; Chen Juan; Xue Liang; Raheela Rehman; Amal Mohamed Al Garawi; et al. (Agricultural Systems, 2024)

Health risk assessment of bread wheat grown under cadmium and nickel stress and impact of silicic acid application on its growth, physiology, and metal uptake - Alina Shafiq; Muhammad Emmad Munawar; Muhammad Nadeem; Asia Khan; Ghulam Hasan Abbasi; Muhammad Anwar ul Haq; Muhammad Ashar Ayub; Irfan Iftikhar; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Effect of naringenin on post-thaw quality, fertility-associated gene expression and fertilization potential of buffalo (Bubalus bubalis) bull sperm - Ghulam Shabbir Khan; Muhammad Zahid Tahir; Muhammad Yasir Zahoor; Hifz-ul-Rahman; Amjad Riaz (Cryobiology, 2024)

Nanoparticle-Mediated Mucosal Vaccination: Harnessing Nucleic Acids for Immune Enhancement - Wajid Hussain; Sadia Chaman; Hafiza Nazia Koser; Syed Muhammad Aun; Zainab Bibi; Ayesha Nasir Pirzadi; Jawad Hussain; Zubaria Zubaria; Ghulam Nabi; Muhammad Wajid Ullah; Shenqi Wang; Ishrat Perveen (Current Microbiology, 2024)

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

First report of Pythium aphanidermatum causing coriander damping-off in district Hyderabad, Sindh, Pakistan - Ghulam Sarwar Shah; Jamal-U-Ddin Hajano; Rehana Naz Syed; Muhammad Ibrahim Khaskheli; Manzoor Ali Abro; Muhammad Ali Khanzada; Abdul Mubeen Lodhi (Journal of Plant Pathology, 2024)

Environmental pollution and officials' promotion: How China's green attention matters - Xue Yang; Peng Zhang; Xiaobo Hu; Ghulam Muhammad Qamri (Journal of Environmental Management, 2024)

The asymmetric effect of global value chain on environmental quality: Implications for environmental management - Qiong Yuan; Helen Huifen Cai; Yan Jiang; Naqib Ullah Khan; Ghulam Muhammad Qamri (Journal of Environmental Management, 2024)

Surviving chlorinated waters: bleaching sensitivity and persistence of free-living amoebae - Muhammad Tariq Zahid; Ghulam Mustafa; Romasa Sajid; Ayesha Razzaq; Muzdalfa Waheed; Moonis Ali Khan; Jae-Hoon Hwang; Young Kwon Park; Woo Jin Chung; Byong-hun Jeon (Environmental Science and Pollution Research, 2024)

Differential growth and biochemical responses induced by benevolent silver nanoparticles in germinating seeds and seedling of Phaseolus vulgaris L. - Muhammad Jamil Ahmed; Ghulam Murtaza (Environment, Development and Sustainability, 2024)

Physicochemical properties and performance of non-woody derived biochars for the sustainable removal of aquatic pollutants: A systematic review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Rashid Iqbal; Faisal Zulfiqar; Akash Tariq; Allah Ditta (Chemosphere, 2024)

The role of fintech, mineral resource abundance, green energy and financial inclusion on ecological footprint in E7 countries: New insight from panel nonlinear ARDL cointegration approach - Songtao Huo; Likun Ni; Muhammad Farhan Basheer; Khalid M. Al-Aiban; Saira Ghulam Hassan (Resources Policy, 2024)

Particulate and gaseous air pollutants exceed WHO guideline values and have the potential to damage human health in Faisalabad, Metropolitan, Pakistan - Nukshab Zeeshan; Ghulam Murtaza; Hamaad Raza Ahmad; Abdul Nasir Awan; Muhammad Shahbaz; Peter Freer-Smith (Environmental Monitoring and Assessment, 2024)
First-ever measurements of particulate matter (PM 2.5 , PM 10 , and TSP) along with gaseous pollutants (CO, NO 2 , and SO 2 ) were performed from June 2019 to April 2020 in Faisalabad, Metropolitan, Pakistan, to assess their seasonal variations; Summer 2019, Autumn 2019, Winter 2019–2020, and Spring 2020. Pollutant measurements were carried out at 30 locations with a 3-km grid distance from the Sitara Chemical Industry in District Faisalabad to Bhianwala, Sargodha Road, Tehsil Lalian, District Chiniot. ArcGIS 10.8 was used to interpolate pollutant concentrations using the inverse distance weightage method. PM 2.5 , PM 10 , and TSP concentrations were highest in summer, and lowest in autumn or winter. CO, NO 2 , and SO 2 concentrations were highest in summer or spring and lowest in winter. Seasonal average NO 2 and SO 2 concentrations exceeded WHO annual air quality guide values. For all 4 seasons, some sites had better air quality than others. Even in these cleaner sites air quality index (AQI) was unhealthy for sensitive groups and the less good sites showed Very critical AQI (> 500). Dust-bound carbon and sulfur contents were higher in spring (64 mg g −1 ) and summer (1.17 mg g −1 ) and lower in autumn (55 mg g −1 ) and winter (1.08 mg g −1 ). Venous blood analysis of 20 individuals showed cadmium and lead concentrations higher than WHO permissible limits. Those individuals exposed to direct roadside pollution for longer periods because of their occupation tended to show higher Pb and Cd blood concentrations. It is concluded that air quality along the roadside is extremely poor and potentially damaging to the health of exposed workers. Graphical abstract

Machine learning assisted improved desalination pilot system design and experimentation for the circular economy - Waqar Muhammad Ashraf; Muhammad Ahmad Jamil; Ghulam Moeen Uddin; Bashar Shboul; Kashif Ishfaq; Kim Choon Ng; Mike Dixon; Ben Bin Xu; Muhammad Wakil Shahzad (Journal of Water Process Engineering, 2024)

Synthesis of polymeric ferrite composites (Ni-CoFe2O4/Chitosan, Zn-NiFe2O4/Starch, Co-NiZnFe2O4/Polyaniline, Ni doped CrZnFe2O4/Alginate, and Cr doped ZnCoFe2O4/PVA) for the removal of reactive golden yellow-160 dye from wastewater - Ghulam Mustafa; Ruba Munir; Bushra Sadia; Fazila Younas; Murtaza Sayed; Amna Muneer; Muhammad Fahad Sardar; Gadah Albasher; Saima Noreen (Journal of Environmental Chemical Engineering, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Assessment of molecular and metabolic traits of a newly isolated Spirulina platensis BERC15 in a low-cost cultivation alternative for its use as functional food - Muhammad Aamer Mehmood; Mahwish Amin; Muhammad Adnan Ul Haq; Ayesha Shahid; Sana Malik; Amna Jabbar Siddiqui; Ning Wang; Hui Zhu; Azhar Rasul; Ahmed Hassan Chaudhry; Khalid Nadeem; Raj Boopathy; et al. (Bioresource Technology Reports, 2024)

Green synthesis of silver nanoparticles for their antifungal activity against anthracnose disease causing Colletotrichum capsici - Anum Haq Nawaz; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Gul-e-lala; Khawaja Shafique Ahmad; Asad Ghulam Nabi (Biocatalysis and Agricultural Biotechnology, 2024)

Unraveling the Endocannabinoid System: Exploring Its Therapeutic Potential in Autism Spectrum Disorder - Ankit Jana; Arnab Nath; Palash Sen; Swikriti Kundu; Badrah S. Alghamdi; Turki S. Abujamel; Muhammad Saboor; Chan Woon-Khiong; Athanasios Alexiou; Marios Papadakis; Mohammad Zubair Alam; Ghulam Md Ashraf (NeuroMolecular Medicine, 2024)
The salient features of autism spectrum disorder (ASD) encompass persistent difficulties in social communication, as well as the presence of restricted and repetitive facets of behavior, hobbies, or pursuits, which are often accompanied with cognitive limitations. Over the past few decades, a sizable number of studies have been conducted to enhance our understanding of the pathophysiology of ASD. Preclinical rat models have proven to be extremely valuable in simulating and analyzing the roles of a wide range of established environmental and genetic factors. Recent research has also demonstrated the significant involvement of the endocannabinoid system (ECS) in the pathogenesis of several neuropsychiatric diseases, including ASD. In fact, the ECS has the potential to regulate a multitude of metabolic and cellular pathways associated with autism, including the immune system. Moreover, the ECS has emerged as a promising target for intervention with high predictive validity. Particularly noteworthy are resent preclinical studies in rodents, which describe the onset of ASD-like symptoms after various genetic or pharmacological interventions targeting the ECS, providing encouraging evidence for further exploration in this area.

Agriculture and environmental management through nanotechnology: Eco-friendly nanomaterial synthesis for soil-plant systems, food safety, and sustainability - Abdul Wahab; Murad Muhammad; Shahid Ullah; Gholamreza Abdi; Ghulam Mujtaba Shah; Wajid Zaman; Asma Ayaz (Science of The Total Environment, 2024)

Effect of biochar, zeolite and bentonite on physiological and biochemical parameters and lead and zinc uptake by maize (Zea mays L.) plants grown in contaminated soil - Sobia Afzal; Suliman Mohammed Suliman Alghanem; Ibtisam Mohammed Alsudays; Zaffar Malik; Ghulam Hassan Abbasi; Ahmad Ali; Sana Noreen; Muhammad Ali; Muhammad Irfan; Muhammad Rizwan (Journal of Hazardous Materials, 2024)

Microalgal and activated sludge processing for biodegradation of textile dyes - Ghulam Mustafa; Muhammad Tariq Zahid; Mayur Bharat Kurade; Aliya Alvi; Faheem Ullah; Nikita Yadav; Hyun-Kyung Park; Moonis Ali Khan; Byong-Hun Jeon (Environmental Pollution, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

RETRACTED: Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Bacteria populating freshly appeared supraglacial lake possess metals and antibiotic-resistant genes - Wasim Sajjad; Nikhat Ilahi; Abdul Haq; Zhanhuan Shang; Ghulam Nabi; Muhammad Rafiq; Ali Bahadur; Abhishek Banerjee; Shichang Kang (Environmental Research, 2024)

Potential of Capparis decidua plant and eggshell composite adsorbent for effective removal of anionic dyes from aqueous medium - Ghulam Mujtaba; Abdul Hai; Mansoor Ul Hassan Shah; Asad Ullah; Yasir Anwar; Furqan Shah; Muhammad Daud; Afzal Hussain; Faheem Ahmed; Fawzi Banat (Environmental Research, 2024)

Preparation and characterization of green silicon nanoparticles and their effects on growth and lead (Pb) accumulation in maize (Zea mays L.) - Haseeba Maryam; Ghulam Hassan Abbasi; Muhammad Waseem; Temoor Ahmed; Muhammad Rizwan (Environmental Pollution, 2024)

Occurrence of diverse plant growth promoting bacteria in soybean [Glycine max (L.) Merrill] root nodules and their prospective role in enhancing crop yield - Mohsin Tariq; Nimra Tahreem; Marriam Zafar; Ghulam Raza; Muhammad Shahid; Muhammad Zunair; Wajeeha Iram; Syeda Tahseen Zahra (Biocatalysis and Agricultural Biotechnology, 2024)

Long-term evaluation of rainfall in the arid region of Pakistan using multi-source data - Ehsan Elahi; Mohammad Ilyas Abro; Murad Ali Khaskheli; Ghulam Abbas Kandhro; Tasneem Zehra; Sikandar Ali; Muhammad Najam Shaikh; Barkat Ali Laghari; Mahdi Hassan; Mushtaque Ahmed Memon (Theoretical and Applied Climatology, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Agro-morphological characterization and genetic variability assessment of soybean [Glycine max (L.) Merr.] germplasm for yield and quality traits - Atta Ullah; Zahid Akram; Ghulam Rasool; Muhammad Waris; Haris Khurshid (Euphytica, 2024)

Hydrochemical, hydrogeological, and cancer health risk analysis of groundwater due to anthropogenic activities, Hasilpur, Pakistan - Muhammad Irfan Jalees; Muhammad Atiq; Muhammad Umar Farooq; Ghulam Hussain; Mehwish Anis; Qurat Ul Ain; Maira Kaleem; Ahmad Ibrahim (Environmental Monitoring and Assessment, 2024)

Synergistic effect of Paclobutrazol and silver nanoparticles (AgNPs) control the pod shattering in canola (Brassica napus L.) via physiological interferences: a mechanistic overview - Habib Ali; Imran Mahmood; Ghulam Qadir; Naveed Iqbal Raja; Fozia Abasi; Mukhtar Ahmed; Muhammad Faizan Ali; Husnain Jawad; Jarosław Proćków (Acta Physiologiae Plantarum, 2024)

Spectrophotometric, microscopic, crystallographic and X-ray based optimization and biological applications of Olea paniculata leaf extract mediated silver nanoparticles - Muhammad Faran Akhtar; Muhammad Irshad; Shaukat Ali; Muhammad Summer; Muhammad Jawad; Muhammad Faizan Akhter; Muhammad Adeel Farooq; Ghulam Asghar (South African Journal of Botany, 2024)

Renewable energy and green economic growth nexus: Insights from simulated dynamic ARDL - Saira Ashfaq; Song Liangrong; Fahad Waqas; Saqib Gulzar; Ghulam Mujtaba; Rana Muhammad Nasir (Gondwana Research, 2024)

Zinc-Coated Urea with Gelatin-Enhanced Zinc Biofortification, Apparent Nitrogen Recovery, and Ryegrass Production - Bilal Abdullah; Muhammad Bilal Khan Niazi; Zaib Jahan; Tariq Shah; Umer Shahzad Malik; Bilal Beig; Abid Mahmood; Ghulam Abbas Shah; Zahid Iqbal (Journal of Soil Science and Plant Nutrition, 2024)

Does financial sector is helpful for curbing carbon emissions through the investment in green energy projects: evidence from MMQR approach - Muhammad Farhan Basheer; Ahsan Anwar; Saria Ghulam Hassan; Ibrahim Tawfeeq Alsedrah; Phan The Cong (Clean Technologies and Environmental Policy, 2024)

Efficient performance of InP and InP/ZnS quantum dots for photocatalytic degradation of toxic aquatic pollutants - Maryam Abbasi; Rukhsanda Aziz; Muhammad Tariq Rafiq; Aziz Ur Rahim Bacha; Zahid Ullah; Abdul Ghaffar; Ghulam Mustafa; Iqra Nabi; Malik Tahir Hayat (Environmental Science and Pollution Research, 2024)

Aligning innovation and information with development: a comparative analysis of developed and developing nations - Muhammad Ghulam Shabeer; Farhat Rasul (Environment, Development and Sustainability, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Insight into microplastics in the aquatic ecosystem: Properties, sources, threats and mitigation strategies - Nisar Ali; Muhammad Hamid Khan; Muhammad Ali; Sidra; Shakeel Ahmad; Adnan Khan; Ghulam Nabi; Farman Ali; Mohamed Bououdina; George Z. Kyzas (Science of The Total Environment, 2024)

Spatially explicit estimation of freshwater fish stock biomass with limited data: A case study of an endangered endemic fish on the Tibetan Plateau, China - Kunyuan Wanghe; Shahid Ahmad; Xin Zhou; Fei Tian; Sijia Liu; Bingzheng Zhou; Ghulam Nabi; Guojie Wang; Kemao Li; Shenglong Jian; Huamin Jiang; Shengxue Chen; et al. (Science of The Total Environment, 2024)

Determination of Salinity Tolerance in Pigmented Rice Genotypes at Seedling Stage - Zeeshan Ali; Muhammad Naeem; Hafiz Ghulam Muhu-Din Ahmed (Journal of Crop Health, 2024)

Phytoremediation of heavy metals spiked soil by Celosia argentea L.: effect on plant growth and metal stabilization - Umer Hussain; Rabia Afza; Iram Gul; Muhammad Anwar Sajad; Ghulam Mujtaba Shah; Zahir Muhammad; Shujaul Mulk Khan (Environmental Science and Pollution Research, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

A holistic approach to embracing the United Nation's Sustainable Development Goal (SDG-6) towards water security in Pakistan - Ghulam Mujtaba; Mansoor Ul Hassan Shah; Abdul Hai; Muhammad Daud; Mazhar Hayat (Journal of Water Process Engineering, 2024)

Development and testing of environment friendly nanohybrid coatings for sustainable agriculture technologies - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Munir Zia; Ghulam Abbas Shah; Ayman A. Ghfar; Zahid Iqbal (Environmental Research, 2024)

Design and Exploration of Benzene Like Azobis Triazoles for Long-range Push-Pull Photo-Switching Attributes - Abrar U. Hassan; Sajjad H. Sumrra; Muhammad Zubair; Ayesha Mohyuddin; Ghulam Mustafa (Journal of Fluorescence, 2023)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Developing Micropropagation Protocols of Date Palm (Phoenix dactylifera L.) cv. Barhi Using Shoot Tip Explants - Najamuddin Solangi; Adel Ahmed Abul-Soad; Mushtaque Ahmed Jatoi; Ghulam Sarwar Markhand; Muhammad Aslam Solangi; Abdul Aziz Mirani (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Spatial distribution of heavy metals, source identification, risk assessment and particulate matter in the M4 motorway - Muhammad Hassan Bashir; Hamaad Raza Ahmad; Ghulam Murtaza; Muhammad Farrakh Nawaz (Environmental Monitoring and Assessment, 2023)

Chromium removal from aqueous solution using bimetallic Bi0/Cu0-based nanocomposite biochar - Behzad Murtaza; Aqsa Naseer; Muhammad Imran; Noor S. Shah; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Muhammad Shahid; Jibran Iqbal; Ghulam Abbas; Natasha Natasha; Muhammad Amjad (Environmental Geochemistry and Health, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Biowaste-based sorbents for arsenic removal from aqueous medium and risk assessment - Maham Akhtar Nagra; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Rabia Naz; Sabah Ansar; Muhammad Shahid; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Nasir Masood; Ghulam Mustafa Shah; et al. (Environmental Geochemistry and Health, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Unrivalled insight into potential biopharmaceutical application of Saussurea albescens (DC.) Sch.Bip.: Chemical profiling, antioxidant and enzyme inhibition activities and in silico studies - Muhammad Imran Tousif; Muhammad Saleem; Saba Tauseef; Mamona Nazir; Tahira Ruby; Reaz Uddin; Sharon Elaine D'souza; Muhammad Aleem Ashraf; Ghulam Mustafa Kamal; Jallat Khan; Gokhan Zengin (Biocatalysis and Agricultural Biotechnology, 2023)

Introducing new green machining technology to enhance process performance and reduce environmental pollution in the metal processing industry - Pengwen Wang; Aqib Mashood Khan; Mohammed Alkahtani; Fahad Alasim; Muhammad Jamil; Ghulam Hussain (Environmental Science and Pollution Research, 2023)

Occurrence and characterization of Alternaria alternata causing leaf spot of soybean (Glycine max) in Pakistan - Muhammad Ismail Buzdar; Nasim Ahmed; Muhammad Jawad Akbar Awan; Saleem. Ur-Rahman; Muhammad Abu Bakar Waqas; Ghulam Raza; Fathia Mubeen; Shahid Mansoor; Imran Amin (Journal of Plant Pathology, 2023)

Biogas Energy Resources in Pakistan Status, Potential, and Barriers - Muhammad Wakeel; Tasawer Hayat; Noor Samad Shah; Jibran Iqbal; Zia Ul Haq Khan; Ghulam Mustafa Shah; Atta Rasool (Utilities Policy, 2023)

Molecular regulation of antioxidants and secondary metabolites act in conjunction to defend plants against pathogenic infection - Muhammad Usman Akbar; Muhammad Aqeel; Muhammad Shahzad Shah; Ghulam Jeelani; Naeem Iqbal; Ammara Latif; Rehab O. Elnour; Mohamed Hashem; Omar Mahmoud Alzoubi; Talaat Habeeb; Muhammad Qasim; Ali Noman (South African Journal of Botany, 2023)

Estimating hardness and Young's modulus of shale using drill cuttings: Implications for hydraulic fracturing in shale gas reservoir development - Ghulam Mohyuddin Sohail; Qamar Yasin; Ahmed E. Radwan; Muhammad Zaka Emad (Gas Science and Engineering, 2023)

Simultaneous adsorption of methylene blue and amoxicillin by starch-impregnated MgAl layered double hydroxide: Parametric optimization, isothermal studies and thermo-kinetic analysis - Ghulam Mujtaba; Asad Ullah; Danish Khattak; Mansoor Ul Hassan Shah; Muhammad Daud; Salman Ahmad; Abdul Hai; Faheem Ahmed; Thamraa Alshahrani; Fawzi Banat (Environmental Research, 2023)

Molecular characterization of azoreductase and its potential for the decolorization of Remazol Red R and Acid Blue 29 - Ghulam Mustafa; Muhammad Tariq Zahid; Mayur Bharat Kurade; Swapnil Mahadeo Patil; Farah Rauf Shakoori; Zeeshan Shafiq; Sidra Ihsan; Yongtae Ahn; Azmat Ali Khan; Amel Gacem; Byong-hun Jeon (Environmental Pollution, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Spatial variability and hydrochemical quality of groundwater of Hyderabad Rural, Sindh, Pakistan - Laeeq Ahmed Khan Khokhar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir Khuhawar; Muhammad Farooque Lanjwani; Ghulam Murtaza Arain; Faiz Muhammad Khokhar; Mezhar Iqbal Khaskheli (Sustainable Water Resources Management, 2023)

Synergistic neuroprotection by phytocompounds of Bacopa monnieri in scopolamine-induced Alzheimer’s disease mice model - Shehla Shoukat; Muhammad Amir Zia; Muhammad Uzair; Roua A. Alsubki; Kaynat Sajid; Sana Shoukat; KOTB A. Attia; Sajid Fiaz; Shaukat Ali; Itoh Kimiko; Ghulam Muhammad Ali (Molecular Biology Reports, 2023)

Palladium nanoparticle formation on boron nitride nanotubes and their photocatalytic performance with visible light - Iqra Rabani; Muhammad Shoaib Tahir; Won-Il Lee; Hai Bang Truong; Ghulam Dastgeer; Young-Soo Seo (Journal of Cleaner Production, 2023)

Biochar alleviated the toxic effects of PVC microplastic in a soil-plant system by upregulating soil enzyme activities and microbial abundance - Attia Rubab Khalid; Tariq Shah; Muhammad Asad; Ahmad Ali; Eisha Samee; Fazal Adnan; Muhammad Faraz Bhatti; Sven Marhan; Claudia I. Kammann; Ghulam Haider (Environmental Pollution, 2023)

Stabilizing anionic redox in Mn-rich P2-type layered oxide material by Mg substitution - Sidra Jamil; Yiming Feng; Muhammad Fasehullah; Ghulam Ali; Bing Wu; Yu-Jie Guo; Bushra Jabar; Adil Mansoor; Yu-Bin Niu; Maowen Xu (Chemical Engineering Journal, 2023)

An Application of Rock Phosphate Increased Soil Cadmium Contamination and Hampered the Morphophysiological Growth of Brassica campestris L - Muhammad Usman Khadim; Ghulam Murtaza; Zia Ur Rahman Farooqi; Tajammal Hussain; Naeem Mahmood; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Molecular and genetic insights into secondary metabolic regulation underlying insect‑pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Molecular and genetic insights into secondary metabolic regulation underlying insect-pest resistance in legumes - Muhammad Khuram Razzaq; Aiman Hina; Asim Abbasi; Benjamin Karikari; Hafiza Javaria Ashraf; Muhammad Mohiuddin; Sumaira Maqsood; Aqsa Maqsood; Inzamam Ul Haq; Guangnan Xing; Ghulam Raza; Javaid Akhter Bhat (Functional & Integrative Genomics, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Recent trends in environmental sustainability - Muhammad Shahid; Hafiz Faiq Bakhat; Ghulam Mustafa Shah; Behzad Murtaza (Environmental Science and Pollution Research, 2023)

Physical properties of multifunctional TM-doped ZnO nanorods and their photocatalytic and anti-bacterial activities - Yasir Zaman; Muhammad Zahid Ishaque; Yasir Yousaf; Muhammad Shahzad; Abu Bakar Siddique; Muhammad Imran Arshad; Muhammad Sajid; Nisar Ali; Ghulam Nabi (Environmental Science and Pollution Research, 2023)

Mycotoxins and consumers’ awareness: Recent progress and future challenges - Kinza Mukhtar; Brera Ghulam Nabi; Sadia Ansar; Zuhaib F. Bhat; Rana Muhammad Aadil; Amin Mousavi Khaneghah (Toxicon, 2023)

Nanobiochar reduces ammonia emission, increases nutrient mineralization from vermicompost, and improves maize productivity - Muhammad Imtiaz Rashid; Ghulam Abbas Shah; Zahid Iqbal; Khurram Shahzad; Nadeem Ali; Mohammad Rehan; Nabil Abdulhafiz A. Alhakamy; Jiří Jaromír Klemeš (Journal of Cleaner Production, 2023)

Bifunctional electrocatalytic water splitting augmented by cobalt-nickel-ferrite NPs-supported fluoride-free MXene as a novel electrocatalyst - Tabinda Rasheed; Aamir Rasheed; Fatimah Mohammed A. Alzahrani; Sara Ajmal; Muhammad Farooq Warsi; M.S. Al-Buriahi; Ghulam Dastgeer; Seung Goo Lee (Fuel, 2023)

Assessment of lithium bioaccumulation by quinoa (Chenopodium quinoa willd.) and its implication for human health - Saira Afzal; Hafiz Faiq Bakhat; Muhammad Shahid; Ghulam Mustafa Shah; Ghulam Abbas (Environmental Geochemistry and Health, 2023)

Impact of biochar amendments on copper mobility, phytotoxicity, photosynthesis and mineral fluxes on (Zea mays L.) in contaminated soils - Zainul Abideen; Hans-Werner Koyro; Faisal Zulfiqar; Anam Moosa; Sarwat Ghulam Rasool; Muhammad Zaheer Ahmad; Muhammad Ahsan Altaf; Nadia Sharif; Ali El-Keblawy (South African Journal of Botany, 2023)

Screening and growth assessment of indigenous and exotic sesame genotypes under osmotic stress - Jahangir Ahmed; Ghulam Qadir; Muhammad Fraz Ali; Talha Javed; Hafiz Muhammad Jhanzab; Fahad Masoud Wattoo; Imran Mahmood; Muhammad Ansar; Muhammad Akram Khan; Usman Zulfiqar; Bilal Ahamad Paray (South African Journal of Botany, 2023)

Testing of Magnetic ZnO/MgFe2O4 Heterostructures for Photocatalytic Removal of Synthetic Dye Pollutants from Wastewater - Muhammad Shoaib; Muhammad Adnan Munir; Muhammad Yasin Naz; Ghulam Abbas; Muhammad Irfan; Saifur Rahman; Abdulnour Ali Jazem Ghanim (Water, Air, & Soil Pollution, 2023)

Screening and validation of salt-stress responsive cg-SSR markers in wheat (Triticum aestivum L.) germplasm of Pakistan - Mishal Khalid; Rehana Kausar; Armghan Shahzad; Ghulam Muhammad Ali; Sania Begum (Molecular Biology Reports, 2023)

Occurrence and risk evaluation of endocrine-disrupting chemicals in wastewater and surface water of Lahore, Pakistan - Muhammad Ashfaq; Yan Li; Muhammad Zubair; Muhammad Saif Ur Rehman; Sajjad Hussain Sumrra; Muhammad Faizan Nazar; Ghulam Mustafa; Muhammad Tahir Fazal; Humayun Ashraf; Qian Sun (Environmental Geochemistry and Health, 2023)

Investigating the environmental externalities of digital financial inclusion and the COVID-19 pandemic: an environmental sustainability perspective - ShiYong Zheng; Bing Sheng; Abdul Ghafoor; Ahsan Ali Ashraf; Ghulam Muhammad Qamri (Environmental Science and Pollution Research, 2023)

From COVID to conflict: Understanding the deriving forces of environment and implications for natural resources - Qasim Raza Khan; Mao Xinshu; Ghulam Muhammad Qamri; Ahmad Nawaz (Resources Policy, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Effects of Biotic and Abiotic Aging Techniques on Physiochemical and Molecular Characteristics of Biochar and Their Impacts on Environment and Agriculture: A Review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Yanyan Li; Akash Tariq; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2023)

Does financial development influence the overall natural environment? An environmental performance index (EPI) based insight from the ASEAN countries - Rana Muhammad Adeel-Farooq; Jimoh Olajide Raji; Ghulam Muhmmad Qamri (Environment, Development and Sustainability, 2023)

The co-application of bioslurry and compost with inorganic zinc fertilizer improved soil quality, zinc uptake, and growth of maize crop - Aqarab Husnain Gondal; Muhammad Imran Khan; Sardar Alam Cheema; Muhammad Iftikhar Hussain; Basharat Ali; Muhammad Nawaz; Muhammad Dawood; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

Application of silicon and sodium hydrosulfide alleviates arsenic toxicity by regulating the physio-biochemical and molecular mechanisms of Zea mays - Aishah Alatawi; Manar Fawzi Bani Mfarrej; Rana M. Alshegaihi; Muhammad Ahsan Asghar; Sahar Mumtaz; Ghulam Yasin; Romina Alina Marc; Shah Fahad; Mohsen Mohamed Elsharkawy; Sadia Javed; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

Microplastics alter soil enzyme activities and microbial community structure without negatively affecting plant growth in an agroecosystem - Tariq Shah; Ahmad Ali; Ghulam Haider; Muhammad Asad; Fazal Munsif (Chemosphere, 2023)

Variation of ionosonde f o E and its comparison with IRI-2016 & a local model over Pakistan longitude sector during solar cycle 22 - Muhammad Ayyaz Ameen; Aisha Ghulam Muhammad; Faizan Abbas; Afnan Tahir; Madeeha Talha (Advances in Space Research, 2023)

Natural pigments: Anthocyanins, carotenoids, chlorophylls, and betalains as colorants in food products - Brera Ghulam Nabi; Kinza Mukhtar; Waqar Ahmed; Muhammad Faisal Manzoor; Muhammad Modassar Ali Nawaz Ranjha; Marek Kieliszek; Zuhaib F. Bhat; Rana Muhammad Aadil (Food Bioscience, 2023)

Effect of Selenium Nanoparticles and Chitosan on Production Performance and Antioxidant Integrity of Heat-Stressed Broiler - Ghulam Murtaza Lochi; Muhammad Ghiasuddin Shah; Jameel Ahmed Gandahi; Javaid Ali Gadahi; Syed Abdul Hadi; Tanzeela Farooq; Waseem Ali Vistro; Mohammad Malyar Rahmani (Biological Trace Element Research, 2023)

Description of novel variants in consanguineous Pakistani families affected with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Irfan Ahmed; Muhammad Iqbal; Shehla Shafqat; Aftab Ahmad Anjum; Wasim Shehzad (Genes & Genomics, 2023)

Unveiling safflower yield, oil content, water use efficiency, and membrane stability under differential irrigation regimes - Muhammad Sajid; Hassan Munir; Abdul Khaliq; Ghulam Murtaza (Arabian Journal of Geosciences, 2023)

Seed-borne Curvularia lunata deteriorating seed health and germination of soybean - Muhammad Ismail Buzdar; Muhammad Jawad Akbar Awan; Saleem Ur Rahman; Rubab Zahra Naqvi; Ghulam Raza; Shahid Mansoor; Imran Amin (Biologia, 2023)

Moving towards sustainability: how do low-carbon energy, current account balance, and reserves induce environmental deterioration in the Big 3? - Mubeen Abdur Rehman; Muhammad Umer Quddoos; Muhammad Sajid Amin; Ghulam Ghouse (Environmental Science and Pollution Research, 2023)

Algae-Mediated Resource Recovery from Urban Wastewater - Muhammad Usman; Mahwish Amin; Iqra Kamal; Ayesha Shahid; Jingliang Xu; Md. Asraful Alam; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf; Raj Boopathy (Current Pollution Reports, 2023)

Micromorphological characterization of seeds of dicot angiosperms from the Thal desert (Pakistan) - Salman Majeed; Mushtaq Ahmad; Fethi Ahmet Ozdemir; Azize Demirpolat; Zeynep Şahan; Trobjon Makhkamov; Muhtor Nasirov; Muhammad Zafar; Shazia Sultana; Ghulam Yaseen; Nabila (Plant Biosystems, 2023)

Metal organic frameworks as promising sensing tools for electrochemical detection of persistent heavy metal ions from water matrices: A concise review - Syed Salman Shafqat; Muhammad Rizwan; Maria Batool; Syed Rizwan Shafqat; Ghulam Mustafa; Tahir Rasheed; Muhammad Nadeem Zafar (Chemosphere, 2023)

Biochar Amendment in Combination with Endophytic Bacteria Stimulates Photosynthetic Activity and Antioxidant Enzymes to Improve Soybean Yield Under Drought Stress - Fahim Nawaz; Rashid Rafeeq; Sadia Majeed; Muhammad Shoaib Ismail; Muhammad Ahsan; Khawaja Shafique Ahmad; Ahsan Akram; Ghulam Haider (Journal of Soil Science and Plant Nutrition, 2023)
The beneficial effects of biochar (BC) and plant growth-promoting bacteria (PGPR) to increase crop yields under harsh environments have been widely reported. However, the knowledge on the synergistic effects of BC and PGPR to induce drought tolerance in oilseeds is scant. In the present study, the effects of cotton sticks derived BC together with PGPR strains ( Paraburkholderia phytofirmans and Bacillus sp.) were examined in water-stressed soybean plants. Initially, the BC application rates (1% and 2%) for soybean were optimized in a pilot experiment (experiment I), and the most effective level (1%) was selected for further studies together with PGPR in the second experiment. The soybean plants were raised in pots under semi-controlled conditions and were subjected to drought stress (25–30% water holding capacity) at pod formation stage. In comparison with control, the drought-mediated decrease in photosynthetic pigments and gas exchange characteristics was markedly lower in BC and PGPR-treated plants. However, the maximum increase in photosynthetic (12–30%) and the enzymatic antioxidant activities (5–20%) was recorded in plants treated with BC + P. phytofirmans , whereas no further significant increase was observed in plants treated with combined BC and Bacillus sp. under water deficit conditions. Similarly, the combined BC and P. phytofirmans application considerably increased the grain yield (14%) under drought stress conditions. We conclude that the combined application of BC + P. phytofirmans could be utilized as an effective strategy to improve soybean yield in dry arid regions.

Floating Treatment Wetlands (FTWs) is an Innovative Approach for the Remediation of Petroleum Hydrocarbons-Contaminated Water - Manar Fawzi Bani Mfarrej; Xiukang Wang; Muhammad Fahid; Muhammad Hamzah Saleem; Aishah Alatawi; Shafaqat Ali; Ghulam Shabir; Rehman Zafar; Muhammad Afzal; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Identification of shoot and root genomic regions in response to nitrogen deficiency tolerance in rice through the use of rice back cross recombinant inbred lines (BRILs) - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Huijie Li; Saba Khanzada; Muhammad Faheem; Mashooq Ali Laghari; Jianmin Bian; Xiaohua Pan; Ziming Wu (Journal of Plant Biochemistry and Biotechnology, 2023)

CRISPR/Cas9 editing of wheat Ppd-1 gene homoeologs alters spike architecture and grain morphometric traits - Aliya Errum; Nazia Rehman; Muhammad Uzair; Safeena Inam; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Functional & Integrative Genomics, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Photocatalytic stimulation of peroxymonosulfate by novel MoO3@ZrO2 with Z-scheme heterojunction for diclofenac sodium degradation - Ghulam Abbas Ashraf; Raqiqa Tur Rasool; Rafiqat Ul Rasool; Muhammad Farooq Saleem; Jazib Ali; Djamel Ghernaout; Muhammad Hassan; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Hai Guo (Journal of Water Process Engineering, 2023)

Small organic molecules as fluorescent sensors for the detection of highly toxic heavy metal cations in portable water - Ramsha Iftikhar; Iqra Parveen; Ayesha; Aqsa Mazhar; Muhammad Saqlain Iqbal; Ghulam Mustafa Kamal; Freeha Hafeez; Ai Ling Pang; Mohsen Ahmadipour (Journal of Environmental Chemical Engineering, 2023)

Sarcococca saligna ameliorated D-galactose induced neurodegeneration through repression of neurodegenerative and oxidative stress biomarkers - Uzma Saleem; Zunera Chauhdary; Sumera Islam; Aimen Zafar; Rana O. Khayat; Norah A. Althobaiti; Ghulam Mujtaba Shah; Mohammed Alqarni; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Antidepressant activity of phytochemicals of Mangifera indica seeds assisted by integrated computational analysis - Uzma Saleem; Shafa Iman; Bashir Ahmad; Muhammad Ajmal Shah; Shabana Bibi; Mohammed Alqarni; Muhammad Saad Khan; Ghulam Mujtaba Shah; Haroon Khan; Reem Hasaballah Alhasani; Norah A. Althobaiti; Aishah E. Albalawi (Metabolic Brain Disease, 2023)

Prosperity risk assessment by heavy metal contamination on human health and multivariate statistical analysis of groundwater as a drinking source - Laeeq Ahmed Khan Khokhar; Muhammad Yar Khuhawar; Taj Muhammad Jahangir; Ghulam Murtaza Arain; Faiz Muhammad Khokhar; Mazhar Iqbal Khaskheli; Shaishta Khan; Muhammad FarooqueLajwani; Muhammad Ilyas Abro; Zahid Ali Zounr (Arabian Journal of Geosciences, 2023)

Impact of seasons and wastewater cultivation on the biomass and biodiesel production by the Plectonema terebrans BERC10 as a candidate for a multiproduct algal biorefinery - Muhammad Nabeel Haider; Aqib Zafar Khan; Muhammad Usman; Deepanraj Balakrishnan; Muhammad Rizwan Javed; Sana Malik; Chen-Guang Liu; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Different feedstocks of biochar affected the bioavailability and uptake of heavy metals by wheat (Triticum aestivum L.) plants grown in metal contaminated soil - Muhammad Ahmar Amin; Ghulam Haider; Muhammad Rizwan; H. Kate Schofield; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Shafaqat Ali (Environmental Research, 2023)

Integrated phycoremediation and ultrasonic-irradiation treatment (iPUT) for the enhanced removal of pharmaceutical contaminants in wastewater - Mayur B. Kurade; Ghulam Mustafa; Muhammad Tariq Zahid; Mukesh Kumar Awasthi; Mital Chakankar; Katrin Pollmann; Moonis Ali Khan; Young Kwon Park; Soon Woong Chang; Woojin Chung; Byong-Hun Jeon (Chemical Engineering Journal, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Recent Advances and Treatment of Emerging Contaminants Through the Bio-assisted Method: A Comprehensive Review - Abdul Sattar Jatoi; Jawad Ahmed; Faheem Akhter; Syed Haseeb Sultan; Ghulam Sever Chandio; Shoaib Ahmed; Zubair Hashmi; Muhammad Azam Usto; Muhammad Shuaib Shaikh; Muhammad Siddique; Ghulamullah Maitlo (Water, Air, & Soil Pollution, 2023)

Analysis of Temperature Data Using the Innovative Trend Pivot Analysis Method and Trend Polygon Star Concept: A Case Study of Soan River Basin, Potohar, Pakistan - Fiaz Hussain; Ray-Shyan Wu; Ghulam Nabi; Rana Shahzad Noor; Muhammad Naveed Anjum; Muhammad Azam; Arslan Afzal (Pure and Applied Geophysics, 2023)
The trend analysis approach is used to estimate changing climate and its impact on the environment, agriculture and water resources. Innovative polygonal trend analyses are qualitative methods applied to detect changes in the environment. In this study, the Innovative Trend Pivot Analysis Method (ITPAM) and Trend Polygon Star Concept Method were applied for temperature trend detection in Soan River Basin (SRB), Potohar region, Pakistan. The average monthly temperature data (1995–2020) for 11 stations were used to create polygon graphics. Trend length and slope were calculated separately for arithmetic mean and standard deviation. The innovative methods produced useful scientific information, with the identification of monthly shifts and trend behaviors of temperature data at different stations. Some stations showed an increasing trend and others showed decreasing behavior. This increasing and decreasing variability is the result of climate change. The winter season temperature is increasing, and the months of December to February are getting warmer. Summer is expanding and pushing autumn towards winter, swallowing the early period of the cold season. The monthly polygonal trends with risk graphs depicted a clear picture of climate change in the Potohar region of Pakistan. The phenomena of observed average temperature changes, indicated by both qualitative methods, are interesting and have the potential to aid water managers’ understanding of the cropping system of the Potohar region.

Biochemical Characterization and Potential of Bacillus safensis Strain SCAL1 to Mitigate Heat Stress in Solanum lycopersicum L. - Tehmeena Mukhtar; Fawad Ali; Mazhar Rafique; Javed Ali; Muhammad Siddique Afridi; Donald Smith; Shehzad Mehmood; Amna; Alfred Souleimanov; Ghulam Jellani; Tariq Sultan; Farooq Hussain Munis; et al. (Journal of Plant Growth Regulation, 2023)

Nickel toxicity pretreatment attenuates salt stress by activating antioxidative system and ion homeostasis in tomato (Solanum lycopersicon L.): an interplay from mild to severe stress - Muhammad Azeem Subhani; Muhammad Amjad; Muhammad Mohsin Iqbal; Behzad Murtaza; Muhammad Imran; Muhammad Asif Naeem; Ghulam Abbas; Mathias Neumann Andersen (Environmental Geochemistry and Health, 2023)

Salinity mitigates cadmium-induced phytotoxicity in quinoa (Chenopodium quinoa Willd.) by limiting the Cd uptake and improved responses to oxidative stress: implications for phytoremediation - Noman Abdal; Ghulam Abbas; Saeed Ahmad Asad; Ayman A. Ghfar; Ghulam Mustafa Shah; Muhammad Rizwan; Shafaqat Ali; Muhammad Shahbaz (Environmental Geochemistry and Health, 2023)

Multiple begomoviruses infecting soybean; a case study in Faisalabad, Pakistan - Saleem U. Rahman; Ghulam Raza; Muhammad Zubair; Nasim Ahmed; Leslie L. Domier; Nousheen Jamil; Shahid Mansoor; Imran Amin (Biologia, 2022)

Plant Growth-Promoting Rhizobacteria Significantly Improves Growth Attributes and Photosynthetic Machinery in Wheat - Tahir Naqqash; Mahreen Fatima; Saif-ur-Rehman; Sherien Bukhat; Muhammad Shahid; Ghulam Shabir; Muhammad Tahir; Muhammad Arshad; Muhammad Babar (Journal of Plant Growth Regulation, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Biomagnification of potentially toxic elements in animals consuming fodder irrigated with sewage water - Ghulam Murtaza; Muhammad Tahir Shehzad; Sobia Kanwal; Zia Ur Rahman Farooqi; Gary Owens (Environmental Geochemistry and Health, 2022)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Analyzing the impact of organizational culture on social sustainability: a perspective of the construction industry - Muhammad Irfan; Wesam Salah Alaloul; Maria Ghufran; Ghulam Yaseen; Muhammad Jamaluddin Thaheem; Abdul Hannan Qureshi; Muhammad Bilal (Environment, Development and Sustainability, 2022)

An analysis of the environmental impacts of ethnic diversity, financial development, economic growth, urbanization, and energy consumption: fresh evidence from less-developed countries - Iftikhar Yasin; Sana Naseem; Muhammad Awais Anwar; Ghulam Rasool Madni; Haider Mahmood; Muntasir Murshed (Environmental Science and Pollution Research, 2022)

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Damage assessment of stored grain pests against rice grains types and wheat - Muhammad Waqar Hassan; Mohsin Ali Hashmi; Ghulam Sarwar; Zahid Mehmood; Warda Saleem; Muhammad Aslam Farooqi (International Journal of Tropical Insect Science, 2022)

Melissopalynological and biochemical profile of honeybee ( Apis mellifera L.) flora in Southern Khyber Pakhtunkhwa, Pakistan - Khushdil Khan; Mushtaq Ahmad; Muhammad Ali; Muhammad Zafar; Ihsan Ul Haq; Alessio Papini; Ghulam Yaseen; Shazia Sultana; Shabir Ahmad; Khafsa Malik (Plant Biosystems, 2022)

Review on integrated disease and pest management of field crops - Muneer Abbas; Muhammad Saleem; Dilbar Hussain; Muhammad Ramzan; Muhammad Jawad Saleem; Sohail Abbas; Niaz Hussain; Muhammad Irshad; Khalid Hussain; Ghulam Ghouse; Mudassar Khaliq; Zubeda Parveen (International Journal of Tropical Insect Science, 2022)

CRISPR-Cas9 based stress tolerance: New hope for abiotic stress tolerance in chickpea (Cicer arietinum) - Muhammad Khuram Razzaq; Muhammad Akhter; Ramala Masood Ahmad; Kaiser Latif Cheema; Aiman Hina; Benjamin Karikari; Ghulam Raza; Guangnan Xing; Junyi Gai; Mohsin Khurshid (Molecular Biology Reports, 2022)

Application of CSM-CANEGRO Model for Climate Change Impact Assessment and Adaptation for Sugarcane in Semi-arid Environment of Southern Punjab, Pakistan - Muhammad Nadeem; Muhammad Nazer Khan; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Ali Raza; Abdul Rehman; Ehsan Ul Haq; Akbar Hayat; Muhammad Ali; Shakeel Ahmad (International Journal of Plant Production, 2022)

Palynological Diversity of Melliferous flora around Apiaries from District Mardan Khyber Pakhtunkhwa-Pakistan - Nabila; Mushtaq Ahmad; Muhammad Ali; Muhammad Zafar; Shazia Sultana; Salman Majeed; Ghulam Yaseen; Shabir Ahmad (The Botanical Review, 2022)

Impact of spatial and temporal changes in climate on the Kunhar River Watershed, Pakistan - Ghulam Nabi; Muhammad Tayyab; Haseeb Akbar; Muhammad Arfan; Ijaz Ahmad; Muhammad Masood; Aqeela Zahra (Arabian Journal of Geosciences, 2022)

Uncovering the role of melatonin in plant stress tolerance - Ahsan Ayyaz; Aneela Kanwal Shahzadi; Saba Fatima; Ghulam Yasin; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Muhammad Ahsan Farooq (Theoretical and Experimental Plant Physiology, 2022)

Systematic significance of seed morphology and foliar anatomy among Acanthaceous taxa - Jamil Raza; Mushtaq Ahmad; Muhammad Zafar; Ghulam Yaseen; Shazia Sultana; Salman Majeed (Biologia, 2022)

Resveratrol and neuroprotection: an insight into prospective therapeutic approaches against Alzheimer’s disease from bench to bedside - Fahadul Islam; Mohamed H. Nafady; Md. Rezaul Islam; Susmita Saha; Salma Rashid; Aklima Akter; Md. Harun- Or-Rashid; Muhammad Furqan Akhtar; Asma Perveen; Ghulam Md. Ashraf; Md. Habibur Rahman; Sherouk Hussein Sweilam (Molecular Neurobiology, 2022)

Nexus between non-renewable energy production, CO2 emissions, and healthcare spending in OECD economies - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir; Ghulam Yahya Khan; Muhammad Usman (Environmental Science and Pollution Research, 2022)

Effect of soil amendments and varied soil texture on wheat growth, physiology, and nutrient accumulation at different salinity: sodicity levels - Ayesha Abdul Qadir; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Ejaz Ahmad Waraich (Arabian Journal of Geosciences, 2022)

A Comparative Analysis of Adopters and Non‐adopters of Drip Irrigation under Plastic Tunnels for Cucumber ( Cucumis sativus L.) Production in Balochistan, Pakistan - Said Qasim; Muhammad Qasim; Anees Hassan; Ghulam Murtaza; Amir Nawaz Khan (Irrigation and Drainage, 2022)
This research tries to compare the water use efficiency, electricity efficiency and economic efficiency of adopters and non‐adopters of drip irrigation under plastic tunnels (DIUPT). Data regarding the socio‐economic conditions of farmers and their views on the advantages and disadvantages of the DIUPT were collected through a questionnaire survey of 200 farmers. For expenses, income, electricity efficiency and water use efficiency, we collected data only from the sample farmers, i.e. one adopter and one non‐adopter. Results also revealed that the total horsepower (HP) hours of water per acre used for drip‐irrigated cucumber under plastic tunnels was 240 compared to 576 HP hours for the flood method of irrigation, thereby saving 58% (336 HP hours) of energy. In other words, with the same amount of water used for irrigating 1 acre of cucumber under flood irrigation, 2.4 acres of cucumber could be irrigated using drip irrigation. Realizing about 51% higher yields under drip irrigation, adopters enjoy 40% higher returns than non‐adopter farmers. The study recommends dissemination of information to farmers about DIUPT through training and seminars. Adoption of these technologies would lead to efficient and sustainable use of already depleting water resources in the drought‐prone province of Balochistan.

Pretreatment with Chitosan Arbitrates Physiological Processes and Antioxidant Defense System to Increase Drought Tolerance in Alfalfa (Medicago sativa L.) - Ghulam Mustafa; Muhammad Asif Shehzad; M. Hammad Nadeem Tahir; Fahim Nawaz; Gulzar Akhtar; Muhammad Asaad Bashir; Abdul Ghaffar (Journal of Soil Science and Plant Nutrition, 2022)

Application of Gypsum or Sulfuric Acid Improves Physiological Traits and Nutritional Status of Rice in Calcareous Saline-Sodic Soils - Ayesha Abdul Qadir; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Ejaz Ahmad Waraich (Journal of Soil Science and Plant Nutrition, 2022)

Bacterial Redox Cycling of Manganese in Calcareous Soil Enhances the Nutrients Bioavailability to Wheat - Saba Babar; Ghulam Jilani; Adil Mihoub; Aftab Jamal; Iftikhar Ahmad; Arshad Nawaz Chaudhary; Muhammad Farhan Saeed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2022)

Cluster bean (Cyamopsis tetragonoloba L.)- a new host of Pythium aphanidermatum - Ghulam Sarwar Shah; Nasir Ahmed Rajput; Rehana Naz Syed; Muhammad Ali Khanzada; Anam Mehwish Khanzada; Owais Iqbal; Abdul Mubeen Lodhi (Journal of Plant Pathology, 2022)

Modelling Climate Uncertainty and Adaptations for Soybean-Based Cropping System - Maryam Ejaz; Ghulam Abbas; Zartash Fatima; Pakeeza Iqbal; Muhammad Ali Raza; Ahmed M. S. Kheir; Mukhtar Ahmed; Khair Muhammad Kakar; Shakeel Ahmad (International Journal of Plant Production, 2022)

Biochar increases salt tolerance and grain yield of quinoa on saline-sodic soil: multivariate comparison of physiological and oxidative stress attributes - Ghulam Abbas; Muhammad Mohsin Abrar; Muhammad Asif Naeem; Manzer H. Siddiqui; Hayssam M. Ali; Yantao Li; Khalil Ahmed; Nan Sun; Minggang Xu (Journal of Soils and Sediments, 2022)

Appraising growth, daily intake, health risk index, and pollution load of Zn in wheat (Triticum aestivum L.) grown in soil differentially spiked with zinc - Abid Ejaz; Zafar Iqbal Khan; Kafeel Ahmad; Fatima Ghulam Muhammad; Shahzad Akhtar; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Exogenous melatonin mitigates chromium toxicity in maize seedlings by modulating antioxidant system and suppresses chromium uptake and oxidative stress - Zaffar Malik; Sobia Afzal; Muhammad Dawood; Ghulam Hassan Abbasi; Muhammad Imran Khan; Muhammad Kamran; Mostafa Zhran; Malik Tahir Hayat; Muhammad Naveed Aslam; Muhammad Rafay (Environmental Geochemistry and Health, 2022)

Assessment of cadmium and lead tolerance potential of quinoa (Chenopodium quinoa Willd) and its implications for phytoremediation and human health - Muhammad Amjad; Muhammad Mohsin Iqbal; Ghulam Abbas; Abu Bakar Umer Farooq; Muhammad Asif Naeem; Muhammad Imran; Behzad Murtaza; Muhammad Nadeem; Sven-Erik Jacobsen (Environmental Geochemistry and Health, 2022)

Cyclo(L-Leucyl-L-Prolyl) from Lactobacillus coryniformis BCH-4 inhibits the proliferation of Aspergillus flavus: an in vitro to in silico approach - Mahwish Salman; Anam Tariq; Ghulam Mustafa; Muhammad Rizwan Javed; Shazia Naheed; Sarmad Ahmad Qamar (Archives of Microbiology, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Correction to: Antioxidant and antibacterial activities of Artemisia absinthium and Citrus paradisi extracts repress viability of aggressive liver cancer cell line - Muhammad Ali; Rida Iqbal; Muhammad Safdar; Sehrish Murtaza; Ghulam Mustafa; Muhammad Sajjad; Shazia Anwer Bukhari; Tayyaba Huma (Molecular Biology Reports, 2022)

Effects of diverse irrigation with wastewater in soil and plants: assessing the risk of metal to the animal food chain - Zafar Iqbal Khan; Fatima Ghulam Muhammad; Kafeel Ahmad; Shahzad Akhtar; Muhammad Sohail; Muhammad Nadeem; Shahzadi Mahpara; Muhammad Umer Farooq Awan; Mona S. Alwahibi; Mohamed S. Elshikh; Muhammad Iftikhar Hussain (Environmental Science and Pollution Research, 2022)

Nickel tolerance and phytoremediation potential of quinoa are modulated under salinity: multivariate comparison of physiological and biochemical attributes - Naila Naheed; Ghulam Abbas; Muhammad Asif Naeem; Munawar Hussain; Rahat Shabbir; Saud Alamri; Manzer H. Siddiqui; Muhammad Zahid Mumtaz (Environmental Geochemistry and Health, 2022)

Feeding niche overlap between native and alien fishes in Swat River, Khyber Pakhtunkhwa, Pakistan - Amir Said; Muhammad Imran; Muhammad Tahir Waseem; Abdul Majid Khan; Noman Khalique; Ghulam Sarwar; Rana Manzoor Ahmad (Environmental Biology of Fishes, 2022)

Biodiversity and ecological interactions of earthworm species from Poonch division Pakistan - Muhammad Umar Khan; Saiqa Andleeb; Muhammad Fiaz Khan; Rozina Ghulam Mustafa (Tropical Ecology, 2022)

Applications of Biotechnology in Food and Agriculture: a Mini-Review - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Waseem Khalid; Hafiz Rehan Nadeem; Ghulam Mueen-ud-Din; Muhammad Zubair Khalid (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Sorghum Water Extract Application Mediates Antioxidant Defense and Confers Drought Stress Tolerance in Wheat - Muhammad Usman Ibrahim; Abdul Khaliq; Saddam Hussain; Ghulam Murtaza (Journal of Plant Growth Regulation, 2022)

Genotypic Differences Among the Rice Genotypes to Arsenic Stress Cultivated Under Two Water Regimes: With an Inference to Human Health - Hafiz Faiq Bakhat; Sidra Arshad; Natasha; Sunaina Abbas; Ghulam Mustafa Shah; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Sajjad; Muhammad Ashfaq; Muhammad Shahid (Journal of Plant Growth Regulation, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

Multivariate analysis of accumulation and critical risk analysis of potentially hazardous elements in forage crops - Muhammad Usman; Behzad Murtaza; Natasha Natasha; Muhammad Imran; Ghulam Abbas; Muhammad Amjad; Muhammad Shahid; Sobhy M. Ibrahim; Gary Owens; Ghulam Murtaza (Environmental Monitoring and Assessment, 2022)

Structural and Functional Annotation of Napin-Like Protein from Momordica charantia to Explore its Medicinal Importance - Rawaba Arif; Muhammad Anjum Zia; Ghulam Mustafa (Biochemical Genetics, 2022)

Feedstock type, pyrolysis temperature and acid modification effects on physiochemical attributes of biochar and soil quality - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman (Arabian Journal of Geosciences, 2022)

Risk characteristics, government subsidies and farmers' willingness to adopt water‐saving irrigation techniques * - Lun Hu; Amanullah Channa; Xiaotong Liu; Ghulam Rasool Lakhan; Muhammad Meraj; Qian Lu; Qingjin Wang (Irrigation and Drainage, 2022)
This paper explores the mechanisms of risk preference, risk awareness and farmers' willingness to adopt water‐saving irrigation techniques in response to government subsidies. Data, collected from farmers in Gansu Province, China, were analysed using mediation and moderation effect models. The empirical evidence from this study indicates that willingness to adopt water‐saving irrigation techniques increased with an increase in government subsidies but decreased with risk awareness due to farmers' attitude of risk preferences. Secondly, the interaction between farmers' risk awareness and risk preference determines their willingness to adopt water‐saving irrigation techniques where risk awareness plays an intermediary role in both cases. Nevertheless, the cautionary role of risk awareness is more obvious, so risk‐averse farmers are significantly less willing to adopt irrigation techniques than risk preference farmers. Also, government subsidies have a significant moderating effect on farmers' risk preferences and risk awareness irrespective of their usage of farming techniques.

The dynamic impact of renewable energy sources on environmental economic growth: evidence from selected Asian economies - Muhammad Khalid Anser; Muhammad Usman; Muhammad Sharif; Sana Bashir; Malik Shahzad Shabbir; Ghulam Yahya Khan; Lydia Bares Lopez (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Salinity modulates lead (Pb) tolerance and phytoremediation potential of quinoa: a multivariate comparison of physiological and biochemical attributes - Azka Iftikhar; Ghulam Abbas; Muhammad Saqib; Arslan Shabbir; Muhammad Amjad; Muhammad Shahid; Iftikhar Ahmad; Shahid Iqbal; Saeed Ahmad Qaisrani (Environmental Geochemistry and Health, 2022)

Antioxidant and antibacterial activities of Artemisia absinthium and Citrus paradisi extracts repress viability of aggressive liver cancer cell line - Muhammad Ali; Rida Iqbal; Muhammad Safdar; Sehrish Murtaza; Ghulam Mustafa; Muhammad Sajjad; Shazia Anwer Bukhari; Tayyaba Huma (Molecular Biology Reports, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

Effects of selenium on the uptake of toxic trace elements by crop plants: A review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Jörg Rinklebe; Daniel C. W. Tsang; Filip M. G. Tack; Ghulam Hasan Abbasi; Afzal Hussain; Avanthi Deshani Igalavithana; Byung Cheon Lee; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2021)

Environmental quality, forestation, and health expenditure: a cross-country evidence - Muhammad Awais Anwar; Ghulam Rasool Madni; Iftikhar Yasin (Environment, Development and Sustainability, 2021)

Melatonin-Induced Salinity Tolerance by Ameliorating Osmotic and Oxidative Stress in the Seedlings of Two Tomato (Solanum lycopersicum L.) Cultivars - Muhammad Ali; Muhammad Kamran; Ghulam Hassan Abbasi; Muhammad Hamzah Saleem; Salman Ahmad; Aasma Parveen; Zaffar Malik; Sobia Afzal; Sunny Ahmar; Khadim Muhammad Dawar; Sardar Ali; Saud Alamri; et al. (Journal of Plant Growth Regulation, 2021)

Health risk assessment of endocrine disruptor bisphenol A leaching from plastic bottles of milk and soft drinks - Muhammad Umar Farooq; Muhammad Irfan Jalees; Qurat-ul-Ain; Ghulam Hussain; Mehwish Anis; Ummara Islam (Environmental Science and Pollution Research, 2021)

Evaluation of the allelopathic effects of leachate from an invasive species (Wedelia triobata) on its own growth and performance and those of a native congener (W. chinensis) - Muhammad Saif Ullah; Jianfan Sun; Susan Rutherford; Ikram Ullah; Qaiser Javed; Ghulam Rasool; Muhammad Ajmal; Daolin Du (Biological Invasions, 2021)

Agricultural water management challenges in the Hunza River Basin: Is a solar water pump an alternative option?* - Madhav Prasad Dhakal; Amjad Ali; Muhammad Zafar Khan; Nisha Wagle; Ghulam Muhammad Shah; Muhammad Mudassar Maqsood; Ajaz Ali (Irrigation and Drainage, 2021)
In the glaciated mountains of the Upper Indus Basin of Pakistan, glacier‐ and snowmelt‐ based irrigation systems have been established over several centuries to secure water for cultivation. However, these systems are now facing several challenges, being sensitive to climate change and thus exposed to the resulting extreme events such as glacial lake outburst floods (GLOFs) and flash floods, also difficult terrain and access paths, male outmigration, limited technical capacity and a weak policy and governance system. Hence, exploring the potential options for overcoming the challenges and irrigating arable barren land could lead to economic prosperity and environmental gains. A literature review, stakeholder consultation and semi‐structured questionnaire survey in two villages of the Hunza River basin was conducted to synthesize information in different domains. Information on the irrigation system and its sources, water distribution/allocation system, challenges and adaptation strategies were collected, and based on community preferences, an alternative irrigation technological package was established to overcome the challenges and irrigate barren land. A customized solar water lifting pump with an efficient micro‐irrigation package was piloted which proved to be climate resilient. The system is simple to adopt, uses clean energy for operation and is economically feasible, with a benefit–cost ratio of 4.96 and a payback period of around 11 years.

The Transition from Arid Farming Systems to Agroforestry Systems in Pakistan: A Comparison of Monetary Returns - Ghulam Abbas; Akhter Ali; Muhammad Khan; Hafiz Zahid Mahmood; Sazali Abdul Wahab; Rafi Amir-ud-Din (Small-scale Forestry, 2021)

Biochar for the Management of Nutrient Impoverished and Metal Contaminated Soils: Preparation, Applications, and Prospects - Ghulam Murtaza; Allah Ditta; Naseer Ullah; Muhammad Usman; Zeeshan Ahmed (Journal of Soil Science and Plant Nutrition, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

Social vulnerability to seismic-tsunami hazards in district Gwadar, Balochistan, Pakistan - Amanullah Mengal; Katsuichiro Goda; Muhammad Ashraf; Ghulam Murtaza (Natural Hazards, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Compact maize canopy improves radiation use efficiency and grain yield of maize/soybean relay intercropping system - Muhammad Ali Raza; Liang Cui; Imran Khan; Atta Mohi Ud Din; Guopeng Chen; Muhammad Ansar; Mukhtar Ahmed; Shakeel Ahmad; Abdul Manaf; John Kwame Titriku; Ghulam Abbas Shah; Feng Yang; et al. (Environmental Science and Pollution Research, 2021)

Deteriorating Habitats and Conservation Strategies to Repopulate the Endangered Indus River Dolphin (Platanista gangetica minor); a Lesson Learned From the Conservation Practices of the Yangtze Finless Porpoise (Neophocaena asiaeorientalis) - Ghulam Nabi; Shahid Ahmad; Richard William McLaughlin; Yujiang Hao; Suliman Khan; Naveed Ahmad; Saeed Ahmad; Muhammad Shoaib Kiani; Yuefeng Wu; Dongming Li (Frontiers in Marine Science, 2021)
The Indus River dolphin (IRD; Platanista gangetica minor ) is an endangered and blind freshwater cetacean, endemic to the Indus River system of Pakistan and India. This review article provides detailed information about the major challenges IRDs are facing, and their possible consequences on the population dynamics of the IRD. Furthermore, we have suggested future conservation strategies for the IRD based on the lesson learned from the conservation of the Yangtze finless porpoise (YFP; Neophocaena asiaeorientalis ), a Critically Endangered freshwater cetacean. The major challenges for IRDs are habitat degradation, habitat fragmentation, and several types of industrial and agricultural pollutants. Worsening climatic changes, illegal fishing, and overfishing are additional threats. The construction of several barrages has fragmented the population into several short segments, some of which are too small for the IRDs to survive. In some segments, the population status of the IRD is unknown. In the remaining populations, genetic inbreeding, water shortage, canal entrapment, and altered ecological environment are potent negative factors for the survival of the IRD. Conservation strategies including fishing bans, translocation, and future research (tagging, periodic health assessments, necropsy and virtopsy, understanding the reproductive biology, and genomics) are possible recommendations. Very serious conservation efforts are needed to save the IRD from decline keeping in view the water shortage, pollution, lack of health assessment studies, and habitat degradation and fragmentation.

Exploring genetic diversity and population structure of Punjab goat breeds using Illumina 50 K SNP bead chip - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ghulam Bilal; Hafiz Muhammad Waheed; Muhammad Sajjad Khan; Muhammad Javaid Asad; Zulfiqar Hussain Kuthu (Tropical Animal Health and Production, 2021)

Phytochemical profiling, in vitro and in vivo anti-inflammatory, analgesic and antipyretic potential of Sesuvium sesuvioides (Fenzl) Verdc. (Aizoaceae) - M. Sajid-ur-Rehman; Saiqa Ishtiaq; Mohsin Abbas Khan; Meshal Alshamrani; Muhammad Younus; Ghazala Shaheen; Muhammad Abdullah; Ghulam Sarwar; Muhammad Sohaib Khan; Faraza Javed (Inflammopharmacology, 2021)

Enhancing socioeconomic resilience and climate adaptation through value chain development of mountain products in Hindu Kush Himalayas - Saranjam M. Baig; Aftab A. Khan; Amjad Ali; Muhammad Zafar Khan; Sultan Ahmed; Ghulam M. Shah; Ghulam Ali (Environment, Development and Sustainability, 2021)

Whole exome sequencing revealed novel variants in consanguineous Pakistani families with intellectual disability - Iqra Ghulam Rasool; Muhammad Yasir Zahoor; Muhammad Iqbal; Aftab Ahmad Anjum; Fatima Ashraf; Hafiz Qamar Abbas; Hafiz Muhammad Azhar Baig; Tariq Mahmood; Wasim Shehzad (Genes & Genomics, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Genome-wide characterization and expression analysis of pseudo-response regulator gene family in wheat - Aliya Errum; Nazia Rehman; Muhammad Ramzan Khan; Ghulam Muhammad Ali (Molecular Biology Reports, 2021)

Identification of genetic variation for salt tolerance in Brassica napus using genome-wide association mapping - Ghulam Mustafa Wassan; Hira Khanzada; Qinghong Zhou; Annaliese S. Mason; Ayaz Ali Keerio; Saba Khanzada; Abdul Malik Solangi; Muhammad Faheem; Donghui Fu; Haohua He (Molecular Genetics and Genomics, 2021)

Optimizing Phosphorus Levels in Wheat Grown in a Calcareous Soil with the Use of Adsorption Isotherm Models - Muhammad Farhan Saeed; Aftab Jamal; Dost Muhammad; Ghulam Mustafa Shah; Hafiz Faiq Bakhat; Iftikhar Ahmad; Sajjad Ali; Fahid Ihsan; Jingkuan Wang (Journal of Soil Science and Plant Nutrition, 2021)

Extent and pattern of damage in wheat caused by three different species of storage insect pests - Muhammad Waqar Hassan; Ghulam Sarwar; Muhammad Aslam Farooqi; Moazzam Jamil (International Journal of Tropical Insect Science, 2021)

Quantification of Climate Warming and Crop Management Impacts on Phenology of Pulses-Based Cropping Systems - Zartash Fatima; Atique-ur-Rehman; Ghulam Abbas; Pakeeza Iqbal; Iqra Zakir; Muhammad Azam Khan; Ghulam Mujtaba Kamal; Mukhtar Ahmed; Shakeel Ahmad (International Journal of Plant Production, 2021)

Experimental investigations of arsenic adsorption from contaminated water using chemically activated hematite (Fe2O3) iron ore - Abdul Qayoom Memon; Shoaib Ahmed; Zulfiqar Ali Bhatti; Ghulamullah Maitlo; Abdul Karim Shah; Shaukat Ali Mazari; Atta Muhammad; Abdul Sattar Jatoi; Ghulam Abbas Kandhro (Environmental Science and Pollution Research, 2021)

Hydrochemistry modelling: evaluation of groundwater quality deterioration due to anthropogenic activities in Lahore, Pakistan - Muhammad Irfan Jalees; Muhammad Umar Farooq; Mehwish Anis; Ghulam Hussain; Arfa Iqbal; Sana Saleem (Environment, Development and Sustainability, 2021)

Disintegration of uncertainties associated with real-time multi-satellite precipitation products in diverse topographic and climatic area in Pakistan - Muhammad Masood; Ghulam Nabi; Muhammad Babur; Aftab Hussain Azhar; Muhammad Kaleem Ullah (Journal of Mountain Science, 2021)

Regional Comparison of Snow Leopard (Panthera uncia) Diet using DNA Metabarcoding - Charlotte E. Hacker; Matthew Jevit; Shafqat Hussain; Ghulam Muhammad; Bariushaa Munkhtsog; Bayaraa Munkhtsog; Yuguang Zhang; Diqiang Li; Yanlin Liu; John D. Farrington; Farida Balbakova; Azat Alamanov; et al. (Biodiversity and Conservation, 2021)

Fungal metabolites as anti-diabetic agents: emphasis on PTP1B inhibitors - Mamona Nazir; Muhammad Saleem; Iftikhar Ali; Ghulam Abbas; Najeeb Ur Rehman; Ivan R. Green; Wahid Hussain; Saima Khan; Hidayat Hussain (Phytochemistry Reviews, 2021)

A research on conventional and modern algorithms for maximum power extraction from wind energy conversion system: a review - Muhammad Zeeshan Malik; Mazhar Hussain Baloch; Mehr Gul; Ghulam Sarwar Kaloi; Sohaib Tahir Chauhdary; Ali Asghar Memon (Environmental Science and Pollution Research, 2021)

Diversity of red palm weevil, Rhynchophorus ferrugineus Oliv. (Coleoptera: Curculionidae) in the Kingdom of Saudi Arabia: studies on the phenotypic and DNA barcodes - Sukirno Sukirno; Muhammad Tufail; Khawaja Ghulam Rasool; Mureed Husain; Abdulrahman Saad Aldawood (International Journal of Tropical Insect Science, 2020)

Sowing Date and Hybrid Choice Matters Production of Maize–Maize System - Ghulam Abbas; Shakeel Ahmad; Mubshar Hussain; Zartash Fatima; Sajjad Hussain; Pakeeza Iqbal; Mukhtar Ahmed; Muhammad Farooq (International Journal of Plant Production, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

Risk assessment of heavy metal(loid)s via Spinacia oleracea ingestion after sewage water irrigation practices in Vehari District - Aneeza Sardar; Muhammad Shahid; Natasha; Sana Khalid; Hasnain Anwar; Muhammad Tahir; Ghulam Mustafa Shah; Muhammad Mubeen (Environmental Science and Pollution Research, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Partial Substitution of Fishmeal with Plant Protein Source the Soybean Meal in the Diets of Arabian Yellowfin Seabream Acanthopagrus arabicus Juveniles - Naveed Ahmad; Jamal Pirzada A. Siddiqui; Ghulam Nabi; Khan Mir Khan; Amjad Ali; Yasmeen Zamir; Mohammad Abdul Momin Siddique; Shabir Ali Amir; Farah Naz Khokhar; Muhammad Amin (Thalassas: An International Journal of Marine Sciences, 2020)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

Soil selenium transformation across different parent materials in Pothwar uplands of Pakistan - Muhammad Imran; Mohammad Saleem Akhtar; Ayaz Mehmood; Shah Rukh; Ahmad Khan; Chen Zhikun; Ghulam Mujtaba (Arabian Journal of Geosciences, 2020)

Genetic mapping and identification of new major loci for tolerance to low phosphorus stress in rice - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Majeeduddin Solangi; Saba Khanzada; Muhammad Faheem; Jianmin Bian; Xiaohua Pan; Rui Cai Han; Xunfeng He; et al. (Physiology and Molecular Biology of Plants, 2020)
Phosphorus (P) is one of the essential macronutrients for rice. In this study, we used 120 rice backcross recombinant inbred lines (BRILs) derived from a cross indica cv. Changhui 891 and japonica cv. 02428. To elucidate the genetic control of P deficiency tolerance in rice, we have used high quality SNPs bin markers to identify some important loci underlying phosphorus deficiency. The bin map was generated which includes 3057 bins covering distance of 1266.5 cM with an average of 0.41 cM between markers. Based on this map, 50 loci, including four novel loci, qSL - 3 , qRL - 11 , qSDW - 1 , qRDW - 1 with phenotypic variance 23.26%, 12.06%, 9.89% associated with P deficiency-related seedling traits were identified. No significant QTLs was found for root length under P+, shoot fresh weight P− and root length, shoot fresh weight for P+, P− and their ratio respectively. Root fresh weight, and root dry weight were strongly correlated to each other, and QTLs for these variables were located on the same chromosome 1 at the same region. Notably, 3 pleiotropic regions is the pioneer of our study, and these regions would facilitate map-based cloning to expedite the MAS selection for developing low phosphorous tolerant varieties. This study not only improves our knowledge about molecular processes associated with P deficiency, but also provides useful information to understand the genetic architecture of low phosphorous tolerance.

First report of pepper leaf curl Bangladesh virus (PepLCBV) associated with cotton leaf curl Multan betasatellite on kidney bean (Phaseolus vulgaris) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Muhammad Zuhaib Khan; Ghulam Raza; Imran Amin; Shahid Mansoor (Journal of Plant Pathology, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

Compositional and health risk assessment of drinking water from health facilities of District Vehari, Pakistan - Behzad Murtaza; Natasha; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Noor Samad Shah; Ghulam Abbas; Muhammad Asif Naeem; Muhammad Amjad (Environmental Geochemistry and Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Codiaeum variegatum in Pakistan harbours pedilanthus leaf curl virus and papaya leaf curl virus as well as a newly identified betasatellite - Afzal Akram; Aqsa Hafeez Khan; Ghulam Rasool; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Archives of Virology, 2020)

Cotton leaf curl Kokhran virus in association with Chili leaf curl betasatellite infecting mungbean (Vigna radiata.) and black gram (Vigna mungo.) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Ghulam Raza; Muhammad Zuhaib Khan; Shahid Mansoor; Imran Amin (Australasian Plant Pathology, 2020)

Synthesis, characterization, and biocompatibility of lanthanum titanate nanoparticles in albino mice in a sex-specific manner - Irum Naz Akram; Sana Akhtar; Ghulam Khadija; Mian Muhammad Awais; Muhammad Latif; Aasia Noreen; Mehwish Mobeen; Fareeha Sajjad; Zahida Sardar; Shahid Iqbal; Muhammad Naeem Ashiq; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Effect of Buried Straw Layer Coupled with Fertigation on Florescence and Yield Parameters of Chinese Cabbage Under Greenhouse Environment - Ghulam Rasool; Xiangping Guo; Zhenchang Wang; Muhammad Hassan; Muhammad Aleem; Qaiser Javed; Sheng Chen (Journal of Soil Science and Plant Nutrition, 2020)

Assessing the climate change impacts and adaptation strategies for rice production in Punjab, Pakistan - Ghulam Shabbir; Tasneem Khaliq; Ashfaq Ahmad; Muhammad Saqib (Environmental Science and Pollution Research, 2020)

Sedimentology of Shahejie Formation, Bohai Bay Basin: a case study of Es1 member in Nanpu Sag - Muhammad Kashif; Yingchang Cao; Guanghui Yuan; Muhammad Asif; Faisal Rehman; Kamran Shehzad; Muhammad Fahad Ullah; Ghulam Mustafa (Carbonates and Evaporites, 2020)

Synergistic Long-Term Temperate Climate Nitrogen Removal Performance in Open Raceway Pond and Horizontal Subsurface Flow Constructed Wetland Operated Under Different Regimes - Raana Fahim; Xiwu Lu; Ghulam Ahmad Jilani; Hasan Mahdi; Muhammad Aslam (Water, Air, & Soil Pollution, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Effect of biochars, biogenic, and inorganic amendments on dissolution and kinetic release of phytoavailable silicon in texturally different soils under submerged conditions - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Ashar Ayub; Tariq Aziz; Muhammad Saqib; Ghulam Murtaza (Arabian Journal of Geosciences, 2020)

Regeneration response of carnation cultivars in response of silver nanoparticles under in vitro conditions - Muhammad Zia; Kamran Yaqoob; Abdul Mannan; Sobia Nisa; Ghulam Raza; Riaz ur Rehman (Vegetos, 2020)

Characterization of antifungal metabolites produced by Lactobacillus plantarum and Lactobacillus coryniformis isolated from rice rinsed water - Shazia Anwer Bukhari; Mahwish Salman; Muhammad Numan; Muhammad Rizwan Javed; Muhammad Zubair; Ghulam Mustafa (Molecular Biology Reports, 2020)

Ameliorative Effects of Biochar on Rapeseed (Brassica napus L.) Growth and Heavy Metal Immobilization in Soil Irrigated with Untreated Wastewater - Muhammad Kamran; Zaffar Malik; Aasma Parveen; Li Huang; Muhammad Riaz; Saqib Bashir; Adnan Mustafa; Ghulam Hassan Abbasi; Bin Xue; Umeed Ali (Journal of Plant Growth Regulation, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Photoperiodic stress induces genotype-specific shift in DNA methylation in Tartary buckwheat - Muhammad Saad; Helen Mary; Umar Amjid; Ghulam Shabir; Kashif Aslam; Shahid Masood Shah; Abdul Rehman Khan (Biologia Futura, 2019)
Tartary buckwheat, known for its rich source of health beneficial secondary metabolites, is cultivated in many areas of the world. Among different environmental factors, photoperiod strongly influence its growth, flowering time, and ultimately the yield. In this context, epigenetics could contribute significantly in the regulation of plant response against changing environment. Therefore, with the aim to study the involvement of DNA methylation in photoperiod mediated plant response, genome-wide DNA methylation analysis was performed in two accessions (A1 and A2) of Tartary buckwheat using three photoperiodic treatments, i.e., 10-hr light/day (T1), 12-hr light/day (T2), and 14-hr light/day (T3). Flowering time and plant fresh weight data revealed that accessions A1 and A2 prefer T1 and T2 treatments, respectively. Total DNA methylation ratio increased with the increase in photoperiod in accession A1 but decreased under same conditions in accession A2. Full methylation increased significantly while intensive decrease in hemimethylation was noted from T2 to T3 in A1, whereas full methylation strongly increased and hemimethylation strongly decreased from T1 to T2 in A2. Overall, the DNA methylation events appeared more frequently than demethylation events. This study reports for the first time an accession-/genotype specific pattern of shift in the DNA methylation under different photoperiodic treatments that will pave the way toward identification of specific genes involved in the regulation of plant response against photoperiodic stress.

Role of Bioactive Peptides in Reducing the Severity of Hypertension with the Inhibition of ACE - Muhammad Zohaib Aslam; Muhammd Shoaib Aslam; Shumaila Firdos; Ghulam Ghous; Gulistan Firdos; Zhao Hongfei; Zhang Bolin (International Journal of Peptide Research and Therapeutics, 2019)

Application of water quality index, synthetic pollution index, and geospatial tools for the assessment of drinking water quality in the Indus Delta, Pakistan - Ghulam Shabir Solangi; Altaf Ali Siyal; Muhammad Munir Babar; Pirah Siyal (Environmental Monitoring and Assessment, 2019)

Heat treatment effects on chilling injury and disease incidence in sweet orange fruits stored at chilling and non-chilling temperatures - Ijaz Hussain; Abdur Rab; Naqib Ullah Khan; Zarina Bibi; Shah Masaud Khan; Naushad Ali; Muhammad Saeed; Sher Aslam Khan; Sardar Ali; Ghulam Dastagir; Muhammad Sajid (Journal of Consumer Protection and Food Safety, 2019)

Different nitrogen and biochar sources’ application in an alkaline calcareous soil improved the maize yield and soil nitrogen retention - Muhammad Farooq Qayyum; Mehak Ameer Abdullah; Muhammad Rizwan; Ghulam Haider; Muhammad Arif Ali; Muhammad Zafar-ul-Hye; Muhammad Abid (Arabian Journal of Geosciences, 2019)

Aloe vera gel enriched with garlic essential oil effectively controls anthracnose disease and maintains postharvest quality of banana fruit during storage - Ghulam Khaliq; Hafiz Tassawar Abbas; Intazar Ali; Muhammad Waseem (Horticulture, Environment, and Biotechnology, 2019)

Toward GIS-Based Approach for Identification of Ecological Sensitivity Areas: Multi-Criteria Evaluation Technique for Promotion of Tourism in Soon Valley, Pakistan - Muhammad Atif Butt; Khadija Nisar; Syed Amer Mahmood; Javed Sami; Jahanzeb Qureshi; Ghulam Jaffer (Journal of the Indian Society of Remote Sensing, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Salinity stress in cotton: effects, mechanism of tolerance and its management strategies - Iram Sharif; Saba Aleem; Jehanzeb Farooq; Muhammad Rizwan; Abia Younas; Ghulam Sarwar; Shahid Munir Chohan (Physiology and Molecular Biology of Plants, 2019)

Foliar uptake of arsenic nanoparticles by spinach: an assessment of physiological and human health risk implications - Natasha; Muhammad Shahid; Camille Dumat; Sana Khalid; Faiz Rabbani; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Abbas; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks - Ashfaq Ahmad; Muhammad Shahid; Sana Khalid; Habiba Zaffar; Tatheer Naqvi; Arshid Pervez; Muhammad Bilal; Muhammad Arif Ali; Ghulam Abbas; Wajid Nasim (Environmental Science and Pollution Research, 2019)

First report of Macrophomina phaseolina causing dry root rot of lentil in Pakistan - Najeeb Ullah; Khalid Pervaiz Akhtar; Muhammad Jawad Asghar; Ghulam Abbas (Journal of Plant Pathology, 2019)

Homotypic Clusters of Transcription Factor Binding Sites in the First Large Intron of AGL24 MADS-Box Transcription Factor Are Recruited in the Enhancement of Floral Expression - Tajammul Hussain; Nazia Rehman; Safeena Inam; Wajya Ajmal; Amber Afroz; Aish Muhammad; Yusuf Zafar; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Plant Molecular Biology Reporter, 2019)

Biogeochemical behavior of nickel under different abiotic stresses: toxicity and detoxification mechanisms in plants - Nuzhat Ameen; Muhammad Amjad; Behzad Murtaza; Ghulam Abbas; Muhammad Shahid; Muhammad Imran; Muhammad Asif Naeem; Nabeel K. Niazi (Environmental Science and Pollution Research, 2019)

The Asian Houbara Bustard (Chlamydotis macqueenii): on an accelerating path to extinction? - Ghulam Nabi; Rahim Ullah; Suliman Khan; Nawsherwan; Muhammad Amin; Naveed Rauf (Biodiversity and Conservation, 2019)

Composting of municipal solid waste by different methods improved the growth of vegetables and reduced the health risks of cadmium and lead - Ghulam Mustafa Shah; Nadia Tufail; Hafiz Faiq Bakhat; Iftikhar Ahmad; Muhammad Shahid; Hafiz Mohkum Hammad; Wajid Nasim; Atika Waqar; Muhammad Rizwan; Renjie Dong (Environmental Science and Pollution Research, 2019)

Assessment of trace elements in urban topsoils of Rawalpindi-Pakistan: a principal component analysis approach - Muhammad Tahir Shehzad; Ghulam Murtaza; Muhammad Shafeeque; Muhammad Sabir; Haq Nawaz; Muhammad Jamal Khan (Environmental Monitoring and Assessment, 2019)

A multivariate analysis of physiological and antioxidant responses and health hazards of wheat under cadmium and lead stress - Behzad Murtaza; Faryal Naeem; Muhammad Shahid; Ghulam Abbas; Noor S. Shah; Muhammad Amjad; Hafiz Faiq Bakhat; Muhammad Imran; Nabeel Khan Niazi; Ghulam Murtaza (Environmental Science and Pollution Research, 2019)

Chemical investigations of Si-rich organic and inorganic amendments and correlation analysis between different chemical composition and Si contents in amendments - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Ghulam Murtaza; Muhammad Ashfaq Wahid (Arabian Journal of Geosciences, 2019)

5-Aminolevulinic Acid-Induced Heavy Metal Stress Tolerance and Underlying Mechanisms in Plants - Shafaqat Ali; Muhammad Rizwan; Abbu Zaid; Muhammad Saleem Arif; Tahira Yasmeen; Afzal Hussain; Muhammad Rizwan Shahid; Syed Asad Hussain Bukhari; Saddam Hussain; Ghulam Hassan Abbasi (Journal of Plant Growth Regulation, 2018)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Pb fractionation and redistribution as affected by applied inorganic amendments under different soil moisture regimes and incubation time in saline–sodic Pb-polluted paddy soil - Muhammad Mazhar Iqbal; Ghulam Murtaza; Tayyaba Naz; Amjad Hussain; Mark Button; Gijs Du Laing (Paddy and Water Environment, 2018)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

Synthesis of Symmetric Bridged Bis-Pyrazolone Based Metal Complex Acid Dyes and their Applications on Leather - Muhammad Ayaz; Muhammad Ayaz; Farman Ali; Aamer Saeed; Asma Khurshid; Ghulam Shabir; Tanveer Ahmad; Syed Asad Raza Kazmi; Hassan Ali Khan (Journal of Fluorescence, 2018)

Effect of biochar on alleviation of cadmium toxicity in wheat (Triticum aestivum L.) grown on Cd-contaminated saline soil - Tahir Abbas; Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Yong Sik Ok; Ghulam Murtaza (Environmental Science and Pollution Research, 2018)

Effect of biochar and quicklime on growth of wheat and physicochemical properties of Ultisols - Zaffar Malik; Zong Yutong; Lu ShengGao; Ghulam Hassan Abassi; Shafaqat Ali; Muhammad Imran khan; Muhammad Kamran; Moazzam Jamil; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

A comparative study to evaluate efficiency of EDTA and calcium in alleviating arsenic toxicity to germinating and young Vicia faba L. seedlings - Marina Rafiq; Muhammad Shahid; Saliha Shamshad; Sana Khalid; Nabeel Khan Niazi; Ghulam Abbas; Muhammad Farhan Saeed; Mazhar Ali; Behzad Murtaza (Journal of Soils and Sediments, 2018)

Effect of humic and fulvic acid transformation on cadmium availability to wheat cultivars in sewage sludge amended soil - Imran Rashid; Ghulam Murtaza; Zahir Ahmad Zahir; Muhammad Farooq (Environmental Science and Pollution Research, 2018)

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Mohammad Saleem; Ghulam Mustafa; Moneeb Ashraf; Ammara Saleem; Bushra Akhtar (Environmental Monitoring and Assessment, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Agroforestry Systems as Alternative Land-Use Options in the Arid Zone of Thal, Pakistan - Muhammad Khan; Hafiz Zahid Mahmood; Ghulam Abbas; Christos A. Damalas (Small-scale Forestry, 2017)

Proteomic approach to address low seed germination in Cyclobalnopsis gilva - Madiha Zaynab; Sonia Kanwal; Muhammad Furqan; Waqar Islam; Ali Noman; Ghulam Muhammad Ali; Nazia Rehman; Sara Zafar; Kalsoom Sughra; Muhammad Jahanzab (Biotechnology Letters, 2017)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Effectiveness of carbon dioxide against different developmental stages of Cadra cautella and Tribolium castaneum - Mureed Husain; Sukirno Sukirno; Khalid Mehmood; Muhammad Tufail; Khawaja Ghulam Rasool; Waleed Saleh Alwaneen; Abdulrahman Saad Aldawood (Environmental Science and Pollution Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Vortex-assisted ionic liquid-based dispersive liquid–liquid microextraction for assessment of chromium species in artificial saliva extract of different chewing tobacco products - Asma Akhtar; Tasneem Gul Kazi; Hassan Imran Afridi; Syed Ghulam Musharraf; Farah Naz Talpur; Noman Khan; Muhammad Bilal; Mustafa Khan (Environmental Science and Pollution Research, 2016)

Multichromic Bis-Axially Extended Perylene Chromophore with Schiff Bases: Synthesis, Characterization and Electrochemical Studies - Ghulam Shabir; Aamer Saeed; Muhammad Arshad; Muhammad Zahid (Journal of Fluorescence, 2016)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Genetic diversity analysis of Pakistan rice (Oryza sativa) germplasm using multiplexed single nucleotide polymorphism markers - Shahid Masood Shah; Muhammad Arif; Kashif Aslam; Ghulam Shabir; Michael J. Thomson (Genetic Resources and Crop Evolution, 2016)

Differential accumulation of potassium results in varied salt-tolerance response in tomato (Solanum lycopersicum L.) cultivars - Muhammad Amjad; Javaid Akhtar; Behzad Murtaza; Ghulam Abbas; Husnain Jawad (Horticulture, Environment, and Biotechnology, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Relationship between rhizosphere acidification and phytoremediation in two acacia species - Ghulam Abbas; Muhammad Saqib; Javaid Akhtar; Ghulam Murtaza; Muhammad Shahid; Amjad Hussain (Journal of Soils and Sediments, 2016)

Remediation of arsenic-contaminated water using agricultural wastes as biosorbents - Muhammad Bilal Shakoor; Nabeel Khan Niazi; Irshad Bibi; Ghulam Murtaza; Anitha Kunhikrishnan; Balaji Seshadri; Muhammad Shahid; Shafaqat Ali; Nanthi S. Bolan; Yong Sik Ok; Muhammad Abid; Fawad Ali (Critical Reviews in Environmental Science and Technology, 2016)

Differential Role of Indolebutyric Acid in Sugarcane Root Development - Ghulam Mustafa; Muhammad Sarwar Khan (Sugar Tech, 2016)

Effect of Rht alleles on wheat grain yield and quality under high temperature and drought stress during booting and anthesis - Fahad Alghabari; Muhammad Zahid Ihsan; Saddam Hussain; Ghulam Aishia; Ihsanullah Daur (Environmental Science and Pollution Research, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Optical, Electrochemical and Thermoanalytical Investigations on Newly-Synthesized Perylene-3,4,9,10-Dianhydride Fluorescent Dyes - Aamer Saeed; Ghulam Shabir; Muhammad Arshad (Journal of Fluorescence, 2015)

WsMAGO2, a duplicated MAGO NASHI protein with fertility attributes interacts with MPF2-like MADS-box proteins - Humera Ihsan; Muhammad Ramzan Khan; Wajya Ajmal; Ghulam Muhammad Ali (Planta, 2015)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

EDTA enhanced plant growth, antioxidant defense system, and phytoextraction of copper by Brassica napus L. - Ume Habiba; Shafaqat Ali; Mujahid Farid; Muhammad Bilal Shakoor; Muhammad Rizwan; Muhammad Ibrahim; Ghulam Hasan Abbasi; Tahir Hayat; Basharat Ali (Environmental Science and Pollution Research, 2015)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Antibacterial Efficacy of Silver Nanoparticles Synthesized by a Green Method Using Bark Extract of Melia azedarach L - Ansar Mehmood; Ghulam Murtaza; Tariq Mahmood Bhatti; Muhammad Raffi; Rehana Kausar (Journal of Pharmaceutical Innovation, 2014)

Allelic variation at loci controlling stripe rust resistance in spring wheat - SANIA BEGUM; MUHAMMAD IQBAL; IFTIKHAR AHMED; MUHAMMAD FAYYAZ; ARMGHAN SHAHZAD; GHULAM M. ALI (Journal of Genetics, 2014)

The challenges of reducing greenhouse gas emissions and air pollution through energy sources: evidence from a panel of developed countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Faiza Sajjad; Muhammad Azhar Khan; Muhammad Zahir Khan (Environmental Science and Pollution Research, 2014)

Does energy consumption contribute to environmental pollutants? evidence from SAARC countries - Ghulam Akhmat; Khalid Zaman; Tan Shukui; Danish Irfan; Muhammad Mushtaq Khan (Environmental Science and Pollution Research, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Risks factors associated with subclinical mastitis in water buffaloes in Pakistan - Riaz Hussain; Muhammad Tariq Javed; Ahrar Khan; Ghulam Muhammad (Tropical Animal Health and Production, 2013)

Functional evolution of cis-regulatory modules of STMADS11 superclade MADS-box genes - Muhammad Ramzan Khan; Ghulam Muhammad Ali (Plant Molecular Biology, 2013)

Loasins A and B, new flavonoids from Eremostachys loasifolia - Uzma Rasheed Mughal; Ghulam Fareed; Arif Zubair; Abdul Malik; Muhammad Ali Versiani; Nighat Afza; Rasool Bakhsh Tareen (Natural Product Research, 2013)

The diversity of Rhizobia, Sinorhizobia and novel non-Rhizobial Paenibacillus nodulating wild herbaceous legumes - Sadia Latif; SamiUllah Khan; Muhammad Naveed; Ghulam Mustafa; Tasmia Bashir; Abdul Samad Mumtaz (Archives of Microbiology, 2013)

Salinity and drought interaction in wheat (Triticum aestivum L.) is affected by the genotype and plant growth stage - Muhammad Saqib; Javaid Akhtar; Ghulam Abbas; Muhammad Nasim (Acta Physiologiae Plantarum, 2013)

Factors affecting yield and composition of camel milk kept under desert conditions of central Punjab, Pakistan - Sibtain Ahmad; Muhammad Yaqoob; Muhammad Qamar Bilal; Muhammad Kasib Khan; Ghulam Muhammad; Li-Guo Yang; Muhammad Tariq (Tropical Animal Health and Production, 2012)

Risk factors associated with prevalence and major bacterial causes of mastitis in dromedary camels (Camelus dromedarius) under different production systems - Sibtain Ahmad; Muhammad Yaqoob; Muhammad Qamar Bilal; Ghulam Muhammad; Li-Guo Yang; Muhammad Kasib Khan; Muhammad Tariq (Tropical Animal Health and Production, 2012)

Calcium invigorates the cadmium-stressed Brassica napus L. plants by strengthening their photosynthetic system - Guanglong Wan; Ullah Najeeb; Ghulam Jilani; Muhammad S. Naeem; Weijun Zhou (Environmental Science and Pollution Research, 2011)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Determination of Arsenic in Scalp Hair of Children and its Correlation with Drinking Water in Exposed Areas of Sindh Pakistan - Tasneem G. Kazi; Jameel A. Baig; Abdul Q. Shah; Muhammad Balal Arain; Muhammad Khan Jamali; Ghulam A. Kandhro; Hassan I. Afridi; Nida F. Kolachi; Sumaira Khan; Sham K. Wadhwa; Faheem Shah (Biological Trace Element Research, 2011)

Application of proteomics to investigate stress-induced proteins for improvement in crop protection - Amber Afroz; Ghulam Muhammad Ali; Asif Mir; Setsuko Komatsu (Plant Cell Reports, 2011)

Evidence of peste des petits ruminants virus (PPRV) infection in Sindh Ibex (Capra aegagrus blythi) in Pakistan as confirmed by detection of antigen and antibody - Muhammad Abubakar; Zahid Iqbal Rajput; Muhammad Javed Arshed; Ghulam Sarwar; Qurban Ali (Tropical Animal Health and Production, 2011)

Ultraviolet-C mediated physiological and ultrastructural alterations in Juncus effusus L. shoots - Ullah Najeeb; Ling Xu; Zammurad I. Ahmed; Muhammad Rasheed; Ghulam Jilani; Muhammad S. Naeem; Weiqi Shen; Weijun Zhou (Acta Physiologiae Plantarum, 2011)

Preparation and evaluation of chicken embryo-adapted fowl adenovirus serotype 4 vaccine in broiler chickens - Muhammad Khalid Mansoor; Iftikhar Hussain; Muhammad Arshad; Ghulam Muhammad (Tropical Animal Health and Production, 2011)

Enhanced resistance against bacterial wilt in transgenic tomato (Lycopersicon esculentum) lines expressing the Xa21 gene - Amber Afroz; Zubeda Chaudhry; Umer Rashid; Ghulam Muhammad Ali; Farhat Nazir; Javaid Iqbal; Muhammad Rashid Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Evaluation of a 3% surf solution (surf field mastitis test) for the diagnosis of subclinical bovine and bubaline mastitis - Ghulam Muhammad; Abeera Naureen; Muhammad Nadeem Asi; Muhammad Saqib; Fazal-ur-Rehman (Tropical Animal Health and Production, 2010)

Coexistence of arbuscular mycorrhizae and dark septate endophytic fungi in an undisturbed and a disturbed site of an arid ecosystem - Muhammad S. Chaudhry; Syed U. Rahman; Muhammad S. Ismaiel; Ghulam Sarwar; Bushra Saeed; Faiz-ul-Hassan Nasim (Symbiosis, 2009)

Leishmanicidal potential of N-substituted morpholine derivatives: Synthesis and structure–activity relationships - Khalid Mohammed Khan; Muhammad Zarrar Khan; Muhammad Taha; Ghulam Murtaza Maharvi; Zafar Saeed Saify; Shahnaz Parveen; Muhammad Iqbal Choudhary (Natural Product Research, 2009)

Estimation of Toxic Metals in Scalp Hair Samples of Chronic Kidney Patients - Tasneem Gul Kazi; Nusrat Jalbani; Naveed Kazi; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Ghulam Abbas Kandhro; Raja Adil Sarfraz; Abdul Qadir Shah; Rehana Ansari (Biological Trace Element Research, 2009)

Fabrication and evaluation of a portable long‐throated flume - Ali Raza; Muhammad Latif; Ghulam Nabi (Irrigation and Drainage, 2007)
This study was conducted to test the performance of a locally fabricated portable long‐throated flume. Flow was measured over a range of 5–70 l s −1 and sharp crested v‐notch weir was used as a reference device. The measured flow was compared with a theoretical rating table generated by WinFlume software for a flume of same specification. The results indicate a difference of −0.20 to +2.04% between the measured and theoretical flow rates. The theoretical rating tables are generated with an error limit of ±2%, therefore the results are acceptable. The results of this study confirmed that portable long‐throated flumes are reliable and can be easily designed, by using the publicly available WinFlume software, and could be fabricated to suit local requirements. Copyright © 2007 John Wiley & Sons, Ltd.

Piperidines: A new class of Urease inhibitors - Khalid Mohammed Khan; Zafar S. Saify; Muhammad Arif Lodhi; Naeem Butt; Shahnaz Perveen; Ghulam Murtaza Maharvi; Muhammad Iqbal Choudhary; Atta-ur-rahman (Natural Product Research, 2006)

A facile and improved synthesis of sildenafil (Viagra) analogs through solid support microwave irradiation possessing tyrosinase inhibitory potential, their conformational analysis and molecular dynamics simulation studies - Khalid M. Khan; Ghulam M. Maharvi; Mahmud T. H. Khan; Shahnaz Perveen; Muhammad I. Choudhary; Atta-ur- Rahman (Molecular Diversity, 2005)

DNA methylation — an essential mechanism in plant molecular biology - Ishfaq Ahmed Hafiz; Muhammad Akbar Anjum; Abdul Ghaffar Grewal; Ghulam Ahmad Chaudhary (Acta Physiologiae Plantarum, 2001)